Resist underlayer film-forming composition, resist underlayer film, method for manufacturing resist underlayer film, method for forming pattern, and method for manufacturing semiconductor device

By using a specific designed resist lower film forming composition, including a polyether compound containing aromatic rings and an organic solvent, the problem of insufficient adhesion between the resist composition and the substrate in the photon nanoimprinting technology is solved, and high mechanical strength, excellent landfill and flatness, and significantly improved gas penetration are achieved.

CN119861529APending Publication Date: 2025-04-22SHIN ETSU CHEMICAL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411449783.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-20
Filing Date
2024-10-17
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the photonanoimprinting technology, the adhesion between the resist composition and the substrate is insufficient, resulting in pattern peeling defects in the demolding step, and it is difficult for the prior art to effectively improve gas penetration.

Method used

A composition for forming a resist lower film is provided, including a polyether compound containing a specific repeating unit and an organic solvent. By selecting a suitable main framework structure and substituent structure, the mechanical strength, landfillability, flatness and gas penetration of the film are optimized.

Benefits of technology

The high mechanical strength, excellent landfill and flatness of the resist lower film are achieved, while maintaining low film density, significantly improving gas penetration and reducing the occurrence of pattern peeling defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119861529A_ABST
    Figure CN119861529A_ABST
Patent Text Reader

Abstract

The invention relates to a composition for forming a resist underlayer film, a resist underlayer film, a method for manufacturing the resist underlayer film, a pattern forming method, and a method for manufacturing a semiconductor device. The present invention addresses the problem of providing a composition for forming a resist underlayer film, said composition being capable of forming a resist underlayer film exhibiting excellent processing resistance and excellent gas permeability. The solution of the present invention is a composition for forming a resist underlayer film, comprising (A) a polyether compound containing a repeating unit represented by general formula (I), and (B) an organic solvent. # imgabs0 # Ar1 is a substituted or unsubstituted aryl group having 6-30 carbon atoms, or the like, R1 is a substituted or unsubstituted linear, branched, or cyclic, saturated or unsaturated divalent hydrocarbon group having 1-20 carbon atoms, or a substituted or unsubstituted linear, branched, or cyclic heteroalkylene group having 1-20 carbon atoms, and n and m are integers of 0 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resist underlayer film forming composition, a resist underlayer film, a method for producing the resist underlayer film, a pattern forming method, and a method for producing a semiconductor device. In particular, the present invention relates to a resist underlayer film forming composition for nanoimprinting that can be used in fine patterning by photo-nanoimprinting in a semiconductor device manufacturing process. Background Art

[0002] In the manufacture of semiconductor devices, MEMS, etc. that require miniaturization, the optical nanoimprinting technology that can form microstructures of the order of several nanometers on a substrate is a focus of attention. In general optical nanoimprinting technology, first, a liquid resist composition is dripped into the pattern forming area on the substrate using an inkjet method, and the droplets of the resist composition are spread on the substrate (pre-smearing). Next, the resist composition is formed using a mold (mold) that is transparent to the irradiated light and has been patterned. At this time, the droplets of the resist composition will spread over the entire range of the gap between the substrate and the mold due to the capillary phenomenon (smearing). The resist composition will also fill (fill) the inside of the concave portion on the mold due to the capillary phenomenon. The time until the smearing and filling are completed is the filling time. After the filling of the resist composition is completed, light is irradiated to harden the resist composition, and then the two are separated. By implementing these steps, a resist pattern with a predetermined shape will be formed on the substrate.

[0003] In the demolding step of the photo-nanoimprinting technology, the adhesion between the resist composition and the substrate is important. If the adhesion between the resist composition and the substrate is low, when the mold is separated in the demolding step, a part of the photocured material obtained by hardening the resist composition will be peeled off while attached to the mold, and there will be a situation where pattern peeling defects occur. In this context, as for the technology of improving the adhesion between the resist composition and the substrate, it has been proposed to form a bonding layer between the resist composition and the substrate as a layer for bonding the resist composition to the substrate (Patent Document 1).

[0004] In addition, Patent Document 2 discloses a reverse process in nanoimprinting. Since Spin On Carbon (SOC) is used as the processed layer, properties such as processing resistance, embedding and flatness become necessary. In addition, the nanoimprinting process on SOC generally involves coating a close-contact layer material for nanoimprinting on the SOC and performing imprinting thereon. In addition, when the mold is pressed against the curable composition (resist), poor shaping and the like may occur due to the generated bubbles, so the generated bubbles must be defoamed. In Patent Document 3, although the oxygen permeability on the mold side is improved, further improvement in defoaming properties is expected with miniaturization. Considering this background, it has been proposed to defoam the gas from the lower film side and seek the development of a lower film with high air permeability (Non-Patent Document 1).

[0005] As for the permeability of gas, if it is a hydrophobic gas, it will be in a hydrophobic film, and if it is a highly hydrophilic gas, it will be in a hydrophilic film, and there will be a tendency for the permeability to increase. As for the gas environment in the step of pressing the mold tightly, relatively hydrophobic gases such as He, H2, N2, and air are selected, so patent documents 4 and 5 propose highly hydrophobic films with high water contact angles as the lower film material. However, these documents do not discuss the actual gas permeability. In fact, there is also the possibility of selecting highly hydrophilic gases such as CO2. On the other hand, as for air permeability, it is known that in addition to hydrophilicity and hydrophobicity, it will also be greatly affected by film density and admixtures.

[0006] Prior art literature

[0007] Patent Literature

[0008] [Patent Document 1] Japanese Patent Application Laid-Open No. 2013-202982

[0009] [Patent Document 2] Japanese Patent Publication No. 2006-524919

[0010] [Patent Document 3] Japanese Patent No. 6703253

[0011] [Patent Document 4] International Publication No. 2021-125036

[0012] [Patent Document 5] International Publication No. 2023-145923

[0013] Non-patent literature

[0014] [Non-patent document 1] Proc. SPIE 10958, Novel Patterning Technologies for Semiconductors, MEMS / NEMS, and MOEMS 2019, 109580H Summary of the invention

[0015] [Problems to be solved by the invention]

[0016] The present invention is made in view of the above situation, and its purpose is to provide a composition for forming a resist underlayer film that can form a resist underlayer film that exhibits excellent processing resistance and excellent gas permeability, a resist underlayer film that is a cured product of a coating film composed of the composition, a method for manufacturing a resist underlayer film using the composition, a pattern forming method, and a method for manufacturing a semiconductor device.

[0017] [Methods to solve the problem]

[0018] In order to solve the above-mentioned problems, the present invention provides a resist underlayer film-forming composition, characterized in that it comprises:

[0019] (A) a polyether compound containing a repeating unit represented by the following general formula (I), and

[0020] (B) an organic solvent;

[0021] [Chemistry 1]

[0022]

[0023] In the general formula (I), Ar1 is a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, a substituted or unsubstituted heteroaryl group having 6 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 30 carbon atoms formed by condensation or bonding with an aliphatic ring or heterocyclic ring, or a substituted or unsubstituted aryl group having 6 to 30 carbon atoms bonded to each other via a linear, branched or cyclic hydrocarbon group, an ether group or a carbonyl group. Ar1 may be one or a combination of multiple groups in the same resin. R1 is a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, or a substituted or unsubstituted linear hydrocarbon group having 1 to 20 carbon atoms. R2 is any one of a substituted or unsubstituted straight-chain, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom; R3 in the same resin may be one or a combination of multiple groups, and is a hydrogen atom, a substituted or unsubstituted straight-chain, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted straight-chain, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted straight-chain, branched or cyclic alkynyl group having 2 to 20 carbon atoms; and n and m are integers greater than 0.

[0024] If it is a polyether compound as above, Ar1 in the main chain of the polymer contains an aromatic ring, so the mechanical strength for withstanding processing (also known as processing resistance) is excellent. On the other hand, by polyetherifying Ar1 using a straight-chain, branched, or cyclic hydrocarbon group or heteroalkylene group, or an ether group represented by R1 as a connecting part, the close stacking and dense cross-linking reaction between the aromatic rings will be suppressed, and the high density of the film can be suppressed. In this way, by appropriately selecting the main skeleton structure and the substituent structure, the opposite performances such as processing resistance and gas permeability can be taken into account. In addition, the R1 and ether groups of the connecting part can be given fluidity, so excellent filling and excellent flatness can also be achieved. Therefore, the present invention can provide a resist lower layer film that can be expected to have good hardness of the film and show mechanical strength that can withstand processing (good processing resistance), excellent filling and flatness, and low film density, and good gas permeability.

[0025] Furthermore, thermal fluidity can be imparted by introducing arbitrary substituents such as R2 and R3. Furthermore, the steric hindrance of the substituents including R3 introduced by separating the arbitrary substituents R2 and the ether structure will further inhibit the close stacking and dense cross-linking reaction between the aromatic rings, and can further inhibit the high density of the film.

[0026] In the above general formula (I), at least one of the above R3 is a structure R selected from the group consisting of the groups shown in the following formula (II-1): II-1 , and in the structure R II-1 When the ratio is set to a, it is ideally 1≤a≤100.

[0027] [Chemistry 2]

[0028]

[0029] In the formula (II-1), * represents a bonding site with an oxygen atom.

[0030] In the above general formula (I), if at least one of R3 is a structure R selected from the group consisting of the groups represented by the above general formula (II-1) II-1 , the steric hindrance can further inhibit the accumulation of aromatic rings, and can prevent the film from becoming high-density. In addition, by blocking the hydroxyl groups, the hydrophobicity can be improved, the affinity with hydrophobic gases such as He and N2 can be improved, and the permeability of these gases can be improved. In addition, the structure R II-1 The one containing an unsaturated bond can impart crosslinking properties to the compound itself. II-1 R3 can provide a hydrophobic resist underlayer film that is self-crosslinkable and has a low film density.

[0031] In the above general formula (I), R3 is a structure R selected from the group consisting of the groups shown in the following formula (II-1): II-1 and a structure R selected from the group consisting of groups represented by the following formula (II-2): II-2 combination, and in the structure R II-1 The ratio is set to a, and the structure R II-2 When the ratio is set to b, it is ideal to satisfy the relationship of 1≤a≤99, 1≤b≤99, and a+b=100.

[0032] [Chemistry 3]

[0033]

[0034] In formula (II-1) and formula (II-2), * represents a bonding site with an oxygen atom.

[0035] If in the above general formula (I), at least one of R3 is a structure R selected from the group consisting of the groups represented by the above general formula (II-2): II-2 If the ring structure is cyclic, the processing resistance is not easily impaired. On the other hand, the ring structure itself has a low density and a large steric hindrance, so the effect of preventing the aromatic rings from being closely adjacent to each other is large, and the film density will be low. In addition, if at least one of R3 is a structure R selected from the group consisting of the groups represented by the above general formula (II-1): II-1 The one containing unsaturated bonds in the above-mentioned compounds will become a self-crosslinkable film. In addition, by capping the hydroxyl group of R3 with these, the polarity of the compound can be reduced, and the permeability of hydrophobic He, H2, N2, air, etc. can be improved. Then, by making R3 a combination of multiple substituents, the crystallinity of the resin can be reduced, and the thermal fluidity can also be improved. That is, by using a composition containing such a compound, a resist lower layer film with low film density, good permeability, excellent processing resistance, filling property, and flatness can be provided.

[0036] In the above general formula (I), R1 is preferably selected from the group consisting of groups represented by the following general formulae (III-1) to (III-3).

[0037] [Chemistry 4]

[0038]

[0039] In formulae (III-1) to (III-3), * represents a bonding site to an oxygen atom.

[0040] In the above general formula (I), if R1 is selected from the group consisting of the groups shown in the above general formulas (III-1) to (III-3), it is not easy to be damaged and has processing resistance because it has a cyclic structure. On the other hand, the cyclic structure itself has a low density and a large steric hindrance, so the effect of preventing aromatic rings from being closely adjacent to each other is large, and a film with low film density will be obtained. That is, this preferred composition can provide a resist underlayer film that exhibits better processing resistance and higher gas permeability.

[0041] In the above general formula (I), Ar1 is preferably selected from the group consisting of structures represented by the following formula (Ar-1).

[0042] [Chemistry 5]

[0043]

[0044] In the formula (Ar-1), * represents a bonding site to the oxygen atom of -O-R1- or OR3.

[0045] The structures represented by the above formula (Ar-1) all have two benzene rings in one structure, so they will show good processing resistance. Then, they are bonded or condensed by alkylene chains or ether chains, and have, for example, a spiro structure that presents a distorted structure in three dimensions, thereby forming a structure that can inhibit the accumulation of aromatic rings, and can inhibit the film from becoming high-density after baking. Therefore, by using this better composition, a resist lower layer film that can show better gas permeability can be provided.

[0046] The polyether compound preferably has a polystyrene-equivalent weight average molecular weight Mw of 2,000 to 12,000 as determined by gel permeation chromatography.

[0047] When the weight average molecular weight Mw of the polyether compound is 2000 to 12000, the amount of low molecular weight components that may become sublimates during baking will decrease, so that poor film formation is less likely to occur and poor filling properties due to reduced thermal fluidity caused by an excessively large molecular weight can be prevented in the resist underlayer film forming composition.

[0048] The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to firing at 180° C. for 60 seconds, and then subjected to additional firing at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and

[0049] After the additional firing, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2.

[0050] Ideally, it is 101<{(FT-2) / (FT-1)}×100.

[0051] If it becomes 101<{(FT-2) / (FT-1)}×100, the reworked membrane will show swelling compared to the membrane just after firing. It is believed that a porous membrane with a large number of fine pores into which diluents such as OK73 can penetrate is formed just after firing, indicating that a membrane with low membrane density is formed rather than a dense membrane.

[0052] It is preferred that (C) a surfactant is further contained.

[0053] The resist underlayer film-forming composition of the present invention can suppress film formation defects such as streaking on the film surface and disturbance of in-plane uniformity by containing the (C) surfactant.

[0054] further comprising (D) a cross-linking agent,

[0055] The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to firing at 180° C. for 60 seconds, and then subjected to additional firing at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and

[0056] After the additional firing, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2.

[0057] Ideally, 100<{(FT-2) / (FT-1)}×100<103.

[0058] When the curing is insufficient with only the polyether compound, the curing can be accelerated by the crosslinking agent (D). In addition to increasing the hardness of the film and enhancing the processing resistance, the swelling of the film after reworking can be suppressed, so the porosity of the film can be adjusted.

[0059] It further contains (E) a thermally decomposable resin,

[0060] The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to firing at 180° C. for 60 seconds, and then subjected to additional firing at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and

[0061] After the additional firing, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2.

[0062] It is also ideal that 101.5<{(FT-2) / (FT-1)}×100.

[0063] The resist underlayer film forming composition of the present invention further comprises (E) a pyrolyzable resin, and the pyrolyzable resin decomposes during baking and sublimates from within the film, so that further pores can be formed within the film. Therefore, in this preferred aspect of the composition, the swelling of the film after reworking becomes greater, so the degree of porosity of the film can be adjusted.

[0064] further comprising (D) a crosslinking agent and (E) a thermally decomposable resin,

[0065] The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to firing at 180° C. for 60 seconds, and then subjected to additional firing at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and

[0066] After the additional firing, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2.

[0067] It may be 100<{(FT-2) / (FT-1)}×100.

[0068] (D) Crosslinking agent and (E) pyrolyzable resin have opposite effects from the viewpoint of adjusting the porosity of the membrane, so when both are contained, it is sufficient as long as the hardening of the membrane can be confirmed. Therefore, when comparing the difference in membrane thickness before and after reworking, (FT-2)>(FT-1) is sufficient.

[0069] It is also preferable to further contain (F) an acid generator.

[0070] By including (F) an acid generator, the curability of the resin and the decomposability of the thermally decomposable resin may be improved.

[0071] The resist underlayer film forming composition of the present invention can also be used for nanoimprinting.

[0072] The use of the resist underlayer film formed by the composition of the present invention is not particularly limited. For example, the resist underlayer film-forming composition of the present invention can also be used for nanoimprinting. The resist underlayer film formed by the resist underlayer film-forming composition of the present invention has good processing resistance, excellent filling and flatness, and low film density and can show good air permeability. Therefore, by using the composition of the present invention, a very useful resist underlayer film for nanoimprinting can be realized.

[0073] Furthermore, the present invention provides a resist underlayer film which is a cured product of a coating film composed of the resist underlayer film forming composition of the present invention.

[0074] The resist underlayer film formed using the resist underlayer film-forming composition of the present invention has good processing resistance, excellent filling property and flatness, and has a low film density and can exhibit good air permeability.

[0075] Furthermore, the present invention provides a method for manufacturing a resist underlayer film, characterized in that it comprises the following steps:

[0076] The resist underlayer film forming composition of the present invention is applied on a semiconductor substrate to obtain a coating film,

[0077] The coated film is fired to obtain a resist underlayer film.

[0078] If this is the method for manufacturing the resist underlayer film of the present invention, since the resist underlayer film-forming composition of the present invention is used, a resist underlayer film having good processing resistance, excellent filling property and flatness, low film density, and good air permeability can be achieved.

[0079] Furthermore, the present invention provides a pattern forming method, characterized in that it comprises the following steps:

[0080] forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition of the present invention,

[0081] forming a hardening composition film on the resist underlayer film,

[0082] The curable composition film is brought into contact with a mold,

[0083] The curable composition film is irradiated with light or electron beam to form a cured film.

[0084] The cured film is separated from the mold.

[0085] By using the pattern forming method of the imprint method of the present invention, it is possible to utilize a resist underlayer film that has good processing resistance, excellent filling property and flatness, low film density, and good air permeability. Therefore, by using the pattern forming method of the imprint method of the present invention, it is possible to quickly remove bubbles generated when the mold is pressed against the curable composition film, and to form a fine pattern.

[0086] The step of forming a curable composition film on the resist underlayer film may include: forming a bonding layer and / or a polysilicon oxide layer containing 99 mass % or less of Si on the resist underlayer film by coating or evaporation, and forming the curable composition film thereon.

[0087] By forming the adhesion layer, pattern peeling can be sufficiently suppressed in the step of separating the mold. In addition, by forming a polysilicon layer containing 99 mass % or less of Si, the optical properties of the film can be adjusted, and reflection control can be performed.

[0088] Furthermore, the present invention provides a method for manufacturing a semiconductor device, characterized by comprising the following steps:

[0089] forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition of the present invention,

[0090] forming a resist film on the resist underlayer film,

[0091] The resist film is irradiated with light or electron beams and then developed to form a resist pattern.

[0092] Using the formed resist pattern as a mask, the resist underlayer film is etched to obtain a patterned underlayer film,

[0093] The semiconductor substrate is processed using the patterned underlying film as a mask.

[0094] Furthermore, the present invention provides a method for manufacturing a semiconductor device, characterized by comprising the following steps:

[0095] forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition of the present invention,

[0096] forming a hard mask on the resist underlayer film,

[0097] Then, a resist film is formed on the hard mask film.

[0098] The resist film is irradiated with light or electron beams and then developed to form a resist pattern.

[0099] The hard mask is etched using the formed resist pattern as a mask to obtain a patterned hard mask,

[0100] Using the patterned hard mask film as a mask, the lower layer film is etched to obtain a patterned resist lower layer film,

[0101] The semiconductor substrate is processed using the patterned resist underlayer film as a mask.

[0102] The resist underlayer film-forming composition of the present invention can provide a resist underlayer film having good processing resistance, excellent filling property and flatness, low film density, and good air permeability, so as mentioned above, it is also useful in a method for manufacturing a semiconductor device using a pattern forming method other than the nanoimprint method, such as a multilayer resist method. That is, by the method for manufacturing a semiconductor device of the present invention, a fine pattern can be formed on a semiconductor substrate.

[0103] [Effects of the Invention]

[0104] As described above, the resist underlayer film-forming composition of the present invention comprises (A) a polyether compound containing a repeating unit structure represented by the general formula (I) and (B) a composition of an organic solvent. Since the polyether compound (A) contains an aromatic ring, sufficient mechanical strength for processing resistance, good embedding property, and good flatness can be achieved. On the other hand, the aromatic ring is polyetherified using a linear, branched, or cyclic hydrocarbon group or heteroalkylene group, or an ether group as a connecting part, which can inhibit the close stacking and dense crosslinking reaction between the aromatic rings, so that the film can be inhibited from becoming high-density. Therefore, if it is a resist underlayer film-forming composition of the present invention, it is possible to provide a resist underlayer film that is expected to have good processing resistance, embedding property, and flatness, and has a low film density and good air permeability.

[0105] In addition, the polyether compound (A) may also have multiple substituents, especially the ether substituent R3 and other substituents R2 on the aromatic ring, which can further hinder the stacking and dense cross-linking reaction. In addition, by having multiple substituents, the crystallinity of the polymer will be suppressed and further thermal fluidity can be imparted.

[0106] The above-mentioned film thickness (FT-1) and the above-mentioned film thickness (FT-2) of the composition for forming the resist underlayer film of the present invention can be, for example, 101<{(FT-2) / (FT-1)}×100. This relationship of film thickness indicates that the film has swelled, indicating that a porous film having fine pores as if a solvent is impregnated has been formed. If a dense curing reaction occurs like a normal resin, there will be no gaps for the solvent to be impregnated, so this kind of swelling will not occur, and the film thickness after reworking will not become extremely thick. Based on the above experience, the composition of the present invention is a porous film as if a solvent is impregnated, the film density will become low, and like the solvent, the gas will seep out of the film and penetrate.

[0107] Furthermore, the resist underlayer film of the present invention exhibits good processing resistance, excellent filling property and planarity, and has a low film density and good gas permeability.

[0108] Furthermore, by using the resist underlayer film forming method of the present invention, a resist underlayer film can be manufactured which exhibits good processing resistance, excellent filling property and flatness, low film density, and good gas permeability.

[0109] Furthermore, according to the pattern forming method of the present invention, bubbles generated when the mold is pressed against the curable composition film can be quickly removed, thereby forming a fine pattern.

[0110] Furthermore, by using the method for manufacturing a semiconductor device of the present invention, a semiconductor device having a fine pattern formed on a semiconductor substrate can be manufactured. DETAILED DESCRIPTION

[0111] As described above, in order to form a resist underlayer film capable of transferring a resist pattern onto a substrate to be processed with higher precision during fine patterning, the development of a resist underlayer film having excellent processing resistance, filling properties, and flatness and high gas permeability is sought.

[0112] The inventors of this application have focused on polymers containing aromatic rings that have sufficient mechanical strength but form dense films due to accumulation, and have repeatedly conducted intensive research considering the introduction of structures that would hinder accumulation. As mentioned above, the optical nanoimprinting technology that can form microstructures of the order of several nanometers on a substrate has attracted attention, but there is a problem of defects caused by bubbles generated when the mold is pressed tightly, and improvements have been made to the gas permeability of the mold side. On the other hand, considering the future miniaturization, etc., only the current improvement on the mold side is not sufficient, and defoaming from the resist lower film side is also considered, but there has been no progress in material development and there are still few material options. The inventors of the present application believe that by using an aromatic compound containing a phenolic hydroxyl group as a core and polyetherifying a linear, branched, or cyclic hydrocarbon group or heteroalkylene group and an ether group as a linking part, sufficient mechanical strength can be obtained by the aromatic ring, and fluidity can be given by the hydrocarbon group or heteroalkylene group and the ether group of the linking part, and the accumulation of the aromatic ring can be suppressed, thereby obtaining a film having good embedding property and flatness, low film density, and excellent gas permeability. Then, it is believed that by etherifying the unreacted hydroxyl group that has not reacted during the polyetherification, further improvement in fluidity and suppression of accumulation can be achieved, and a resist underlayer film-forming composition having more excellent embedding property, flatness, and gas permeability can be obtained.

[0113] Based on this idea, the inventors of the present application have further repeated and intensive research and found that if the composition contains: (A) a polyether compound containing a repeating unit represented by the following general formula (I), and (B) an organic solvent, it will become a composition for forming a resist underlayer film that can achieve a resist underlayer film having mechanical strength that can withstand processing, excellent filling properties and flatness, low film density, and good gas permeability, thereby completing the present invention.

[0114] That is, the present invention is a resist underlayer film-forming composition, characterized by comprising:

[0115] (A) a polyether compound containing a repeating unit represented by the following general formula (I), and

[0116] (B) Organic solvent.

[0117] [Chemistry 6]

[0118]

[0119] In the general formula (I), Ar1 is a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, a substituted or unsubstituted heteroaryl group having 6 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 30 carbon atoms formed by condensation or bonding with an aliphatic ring or heterocyclic ring, or a substituted or unsubstituted aryl group having 6 to 30 carbon atoms bonded to each other via a linear, branched or cyclic hydrocarbon group, an ether group or a carbonyl group. Ar1 may be one or a combination of multiple groups in the same resin. R1 is a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, or a substituted or unsubstituted linear hydrocarbon group having 1 to 20 carbon atoms. R2 is any one of a substituted or unsubstituted straight-chain, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom; R3 in the same resin may be one or a combination of multiple groups, and is a hydrogen atom, a substituted or unsubstituted straight-chain, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted straight-chain, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted straight-chain, branched or cyclic alkynyl group having 2 to 20 carbon atoms; and n and m are integers greater than 0.

[0120] Hereinafter, the present invention will be described in detail, but the present invention is not limited thereto.

[0121] <Resist Underlayer Film Forming Composition>

[0122] The composition for forming a resist underlayer film for nanoimprinting of the present invention is a composition for forming a resist underlayer film, characterized in that it comprises: (A) a polyether compound containing a repeating unit represented by the following general formula (I), and

[0123] (B) Organic solvent.

[0124] [Chemistry 7]

[0125]

[0126] In the general formula (I), Ar1 is a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, a substituted or unsubstituted heteroaryl group having 6 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 30 carbon atoms formed by condensation or bonding with an aliphatic ring or heterocyclic ring, or a substituted or unsubstituted aryl group having 6 to 30 carbon atoms bonded to each other via a linear, branched or cyclic hydrocarbon group, an ether group or a carbonyl group. Ar1 may be one or a combination of multiple groups in the same resin. R1 is a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, or a substituted or unsubstituted linear hydrocarbon group having 1 to 20 carbon atoms. R2 is any one of a substituted or unsubstituted straight-chain, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom; R3 in the same resin may be one or a combination of multiple groups, and is a hydrogen atom, a substituted or unsubstituted straight-chain, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted straight-chain, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted straight-chain, branched or cyclic alkynyl group having 2 to 20 carbon atoms; and n and m are integers greater than 0.

[0127] If it is a polyether compound as above, Ar1 in the main chain of the polymer contains an aromatic ring, so the mechanical strength for withstanding processing (also known as processing resistance) is excellent. On the other hand, by polyetherifying Ar1 using a straight-chain, branched, or cyclic hydrocarbon group or heteroalkylene group, or an ether group represented by R1 as a connecting part, the close stacking and dense cross-linking reaction between the aromatic rings will be suppressed, and the high density of the film can be suppressed. In this way, by appropriately selecting the main skeleton structure and the substituent structure, the opposite performances such as processing resistance and gas permeability can be taken into account. In addition, the R1 and ether groups of the connecting part can be given fluidity, so excellent filling and excellent flatness can also be achieved. Therefore, the present invention can provide a resist lower layer film that can be expected to have good hardness of the film and show mechanical strength that can withstand processing (good processing resistance), excellent filling and flatness, and low film density, and good gas permeability.

[0128] Furthermore, thermal fluidity can be imparted by introducing arbitrary substituents such as R2 and R3. Furthermore, the steric hindrance of the substituents including R3 introduced by separating the arbitrary substituents R2 and the ether structure will further inhibit the close stacking and dense cross-linking reaction between the aromatic rings, and can further inhibit the high density of the film.

[0129] By means of the resist underlayer film forming composition of the present invention, a resist underlayer film that can be used in various pattern forming methods can be formed. For example, the resist underlayer film formed by the resist underlayer film forming composition of the present invention can also be used as a resist underlayer film in a pattern forming method using a multilayer resist process, can also be used as a resist underlayer film in a pattern forming method using a nanoimprint method, and can also be used in pattern forming methods other than these. In particular, as previously described, the resist underlayer film formed by the resist underlayer film forming composition of the present invention has good processing resistance, excellent filling and flatness, and has a low film density and can exhibit good air permeability. Therefore, by means of the resist underlayer film forming composition of the present invention, a resist underlayer film that is very useful for nanoimprinting can be realized.

[0130] Hereinafter, each component of the resist underlayer film forming composition of the present invention will be described in more detail.

[0131] <(A) Polyether Compound>

[0132] In the above general formula (I), Ar1 is a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, a substituted or unsubstituted heteroaryl group having 6 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 30 carbon atoms formed by condensation or bonding with an aliphatic ring or heterocyclic ring, or a substituted or unsubstituted aryl group having 6 to 30 carbon atoms bonded to each other via a linear, branched or cyclic hydrocarbon group, an ether group or a carbonyl group. Ar1 may be one type or a combination of multiple types in the same resin. In terms of improving the strength to cope with processing, Ar1 is preferably naphthalene rather than benzene, and anthracene rather than naphthalene. In terms of gas permeability, it is more preferable that multiple benzenes and / or naphthalenes are bonded or condensed via a linear, branched or cyclic alkylene group or ether group.

[0133] In the above general formula (I), R2 is arbitrarily any one of a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom. R2 is preferably a hydrocarbon group from the viewpoint of suppressing stacking, and a cyclic hydrocarbon group is more preferably if the processing resistance is also considered. In addition, R2 is preferably a halogen atom from the viewpoint of improving the hydrophobicity of the film, and a fluorine atom is particularly preferred.

[0134] In the above general formula (I), the specific structure of Ar1 including R2 includes the following structures, but is not limited thereto: * represents a bonding site to an oxygen atom in the polymer main chain or a bonding site to an oxygen atom of an optional substituent OR3.

[0135] [Chemistry 8]

[0136]

[0137] [Chemistry 9]

[0138]

[0139] [Chemistry 10]

[0140]

[0141] In the above general formula (I), R1 is a substituted or unsubstituted straight-chain, branched or cyclic, saturated or unsaturated divalent hydrocarbon group with 1 to 20 carbon atoms, or a substituted or unsubstituted straight-chain, branched or cyclic heteroalkylene group with 1 to 20 carbon atoms. From the perspective of suppressing the accumulation of aromatic rings and maintaining processing resistance, R1 is preferably a cyclic hydrocarbon group or heteroalkyl group. In addition, from the perspective of thermosetting properties, it is more ideal for R1 to contain an unsaturated bond. Then, multiple R1s can also be used in combination in the same resin. By combining multiple R1s, improvements in solubility and thermal fluidity can be expected.

[0142] In the above general formula (I), the specific structure of R1 includes the following structures, but is not limited to these structures. * represents a bonding site with an oxygen atom.

[0143] [Chemistry 11]

[0144]

[0145] In the above general formula (I), R1 is particularly preferably selected from the group consisting of groups represented by the following general formulae (III-1) to (III-3).

[0146] [Chemistry 12]

[0147]

[0148] In formulae (III-1) to (III-3), * represents a bonding site to an oxygen atom.

[0149] In the above general formula (I), if R1 is selected from the group consisting of the groups shown in the above general formulas (III-1) to (III-3), it is not easy to be damaged and has good processing resistance because of the cyclic structure. On the other hand, the cyclic structure itself has low density and large steric hindrance, so the effect of preventing aromatic rings from being closely adjacent to each other is large, and a film with low film density will be formed. That is, this preferred composition can provide a resist underlayer film that exhibits better processing resistance and higher gas permeability.

[0150] In the above general formula (I), R3 may be one or a combination of multiple types in the same resin, and may be a hydrogen atom, a substituted or unsubstituted straight-chain, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted straight-chain, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted straight-chain, branched or cyclic alkynyl group having 2 to 20 carbon atoms. From the perspective of thermosetting properties, R3 is preferably an alkenyl group or an alkynyl group. From the perspective of suppressing the accumulation of aromatic rings, R3 is preferably a branched or cyclic alkyl group, and from the perspective of maintaining processing resistance, a cyclic alkyl group is more preferably.

[0151] In the above general formula (I), the specific structure of R3 includes the following structures, but is not limited to these structures. * represents a bonding site with an oxygen atom.

[0152] [Chemistry 13]

[0153]

[0154] In the above general formula (I), at least one of the above R3 is a structure R selected from the group consisting of the groups shown in the following formula (II-1): II-1 , and in the structure R II-1 When the ratio is set to a, it is ideally 1≤a≤100.

[0155] [Chemistry 14]

[0156]

[0157] In the formula (II-1), * represents a bonding site with an oxygen atom.

[0158] If in the above general formula (I), at least one of R3 is a structure R selected from the group consisting of the groups represented by the above general formula (II-1): II-1 , the steric hindrance can further inhibit the accumulation of aromatic rings, and can prevent the film from becoming high-density. In addition, by blocking the hydroxyl groups, the hydrophobicity can be improved, the affinity with hydrophobic gases such as He and N2 can be improved, and the permeability of these gases can be improved. In addition, the structure R II-1 The one containing an unsaturated bond can impart crosslinking properties to the compound itself. II-1 R3 can provide a hydrophobic resist underlayer film that is self-crosslinkable and has a low film density.

[0159] In the above general formula (I), R3 is a structure R selected from the group consisting of the groups shown in the following formula (II-1): II-1 and a structure R selected from the group consisting of groups represented by the following formula (II-2): II-2combination, and in the structure R II-1 The ratio is set to a, and the structure R II-2 When the ratio is set to b, it is also ideal to satisfy the relationship of 1≤a≤99, 1≤b≤99, and a+b=100.

[0160] [Chemistry 15]

[0161]

[0162] In formula (II-1) and formula (II-2), * represents a bonding site with an oxygen atom.

[0163] In the above general formula (I), at least one of R3 is a structure R selected from the group consisting of the groups represented by the above general formula (II-2) II-2 If the ring structure is cyclic, the processing resistance is not easily impaired. On the other hand, the ring structure itself has a low density and a large steric hindrance, so the effect of preventing the aromatic rings from being closely adjacent to each other is large, and the film density will be low. In addition, if at least one of R3 is a structure R selected from the group consisting of the groups represented by the above general formula (II-1): II-1 The one containing unsaturated bonds in the above-mentioned compounds will become a self-crosslinkable film. In addition, by capping the hydroxyl group of R3 with these, the polarity of the compound can be reduced, and the permeability of hydrophobic He, H2, N2, air, etc. can be improved. Then, by making R3 a combination of multiple substituents, the crystallinity of the resin can be reduced, and the thermal fluidity can also be improved. That is, by using a composition containing such a compound, a resist lower layer film with low film density, good permeability, excellent processing resistance, filling property, and flatness can be provided.

[0164] In the above general formula (I), R3 is a structure R selected from the group consisting of groups represented by the above general formula (II-1) from the viewpoint of thermal curability. II-1 The one containing an unsaturated bond is more preferable. From the viewpoint of maintaining processing resistance, reducing film density, and improving thermal fluidity, the structure R is selected from the group consisting of the groups represented by the above general formula (II-2): II-2 Therefore, if the structure R is contained in R3 at a ratio that can ensure the hardening property of the composition, II-1 If the remaining R3 is a structure R selected from the group consisting of the groups shown in the above general formula (II-2): II-2 That is, from the structure R II-1 and structure R II-2As for the ratio of the combination of structures selected, the ratio that can guarantee the curability of the resin alone to the minimum is more ideal. Specifically, it is ideal to satisfy the relationship of 1≤a≤99, 1≤b≤99, and a+b=100, it is more ideal to satisfy the relationship of 30≤a≤90, a+b=100, and it is particularly ideal to satisfy the relationship of 50≤a≤80, a+b=100.

[0165] In the above general formula (I), n and m are integers greater than 0. n is preferably 1 or more and 2 or less from the viewpoint of imparting thermal curability and steric hindrance by the ether structure. m is more preferably 0 or more and 4 or less. m is more preferably 2 or more for the same reason as n, but may be 0 from the viewpoint of raw material availability.

[0166] For example, in the above general formula (I), Ar1 is preferably selected from the group consisting of structures represented by the following formula (Ar-1).

[0167] [Chemistry 16]

[0168]

[0169] In the formula (Ar-1), * represents a bonding site to the oxygen atom of -O-R1- or OR3.

[0170] The structures represented by the above formula (Ar-1) all have two benzene rings in one structure, so it can be expected that it will show good processing resistance. Then, it has a spiral structure that is, for example, distorted in three dimensions, by bonding or shrinking a straight chain, branched, or cyclic alkylene chain or ether chain, thereby forming a structure that can inhibit the accumulation of aromatic rings, and can inhibit the film from becoming high density after baking. Therefore, by using this better composition, a resist lower layer film with low film density after baking and better air permeability can be provided.

[0171] When Ar1 is a combination of multiple numbers in the same resin of the polyether compound (A), the polyether compound (A) may also contain multiple repeating units with different Ar1 in the same resin. Similarly, when R3 is a combination of multiple numbers in the same resin of the polyether compound (A), the polyether compound (A) may also contain multiple repeating units with different R3 in the same resin.

[0172] <Synthesis method>

[0173] The above-mentioned (A) polyether compound can be synthesized by, for example, using a derivative (X) of Ar1 containing a hydroxyl group, a reagent X-R1-X (Y) which is a dihalogenated alkyl group or a di-p-toluenesulfonic acid alkyl ester or a di-methanesulfonic acid alkyl ester, and a catalyst to carry out a polyetherification reaction (STEP1), and using a polymer obtained by polyetherification, a reagent R3-X (Z) which is a halogenated alkyl group or a p-toluenesulfonic acid alkyl ester or a methanesulfonic acid alkyl ester, and a catalyst to carry out an etherification reaction (STEP2). (R1, R2, R3, n and m are the same as those described above, and X is a halogen group, a methanesulfonyl group or a p-toluenesulfonyl group. R3-X can use two or more types, but only one type is described in the description.

[0174] (STEP1)

[0175] [Chemistry 17]

[0176]

[0177] (STEP2)

[0178] [Chemistry 18]

[0179]

[0180] When performing the above-mentioned (STEP1), the amount of the reagent (Y) used is preferably 0.6 to 0.95 equivalents relative to the derivative (X), and more preferably 0.7 to 0.9 equivalents. When the amount of the reagent (Y) used is set within a preferred range, a portion of the hydroxyl groups that are not consumed in the polyetherification will remain after the termination of (STEP1). For example, in the following formula, if 1 equivalent of resorcinol (2 equivalents of hydroxyl groups) as a derivative (X) is reacted with 0.9 equivalents of dibromobutane (1.8 equivalents of reaction points with hydroxyl groups) as a reagent (Y), 0.2 equivalents of hydroxyl groups that are not consumed in the polyetherification will remain. If 1 equivalent of phloroglucinol (3 equivalents of hydroxyl groups) as a derivative (X) is reacted with 0.9 equivalents of dibromohexane (1.8 equivalents of reaction points with hydroxyl groups) as a reagent (Y), 1.2 equivalents of hydroxyl groups that are not consumed in the polyetherification will remain. In particular, in the case of phloroglucinol, although it is described in the description that one hydroxyl group is not polyetherified, in reality, there are some that are not polyetherified, some that are polyetherified at only one site, and some that are polyetherified at all three sites. These hydroxyl residues can be etherified by the above (STEP 2), and the following shows a reaction example when propargyl bromide is used as a reagent (Z) for resorcinol, and a reaction example when propargyl bromide and hexyl bromide are used as reagents (Z) for phloroglucinol.

[0181] STEP 1 for resorcinol

[0182] [Chemistry 19]

[0183]

[0184] Step 1 for phloroglucinol

[0185] [Chemistry 20]

[0186]

[0187] STEP 2 for resorcinol

[0188] [Chemistry 21]

[0189]

[0190] Step 2 for phloroglucinol

[0191] [Chemistry 22]

[0192]

[0193] The polyetherification reaction using the derivative (X), the reagent (Y) and the catalyst can usually be carried out without a solvent or in a solvent using a base as a catalyst, at room temperature or, if necessary, under cooling or heating. Examples of the solvent used in STEP 1 include alcohols such as methanol, ethanol, isopropanol, butanol, ethylene glycol, propylene glycol, diethylene glycol, glycerol, methyl cellosolve, ethyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether, ethers such as diethyl ether, dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, and 1,4-dioxane, chlorine-based solvents such as dichloromethane, chloroform, dichloroethane, and trichloroethylene, hydrocarbons such as hexane, heptane, benzene, toluene, xylene, and cumene, nitriles such as acetonitrile, ketones such as acetone, ethyl methyl ketone, and isobutyl methyl ketone, esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate, lactones such as γ-butyrolactone, and aprotic polar solvents such as dimethyl sulfoxide, N,N-dimethylformamide, hexamethylphosphoramide, and N-methylpyrrolidone. As the solvent, one of these may be used alone, or two or more of these may be used in mixture. These solvents may be used, for example, in an amount within a range of 0 to 3000 parts by mass based on 100 parts by mass of the reaction raw materials.

[0194] As for the base catalyst used in STEP1, examples include inorganic bases such as sodium hydroxide, potassium hydroxide, barium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, lithium hydride, sodium hydride, potassium hydride, calcium hydride, etc., alkyl metals such as methyl lithium, n-butyl lithium, methyl magnesium chloride, ethyl magnesium bromide, etc., alkoxides such as sodium methoxide, sodium ethoxide, potassium tert-butoxide, triethylamine, diisopropylethylamine, N,N-dimethylaniline, pyridine, 4-dimethylaminopyridine, etc. The amount used is, for example, 0.1 to 1.5 equivalents relative to the amount of hydroxyl groups in the raw material, preferably in the range of 1.0 to 1.05 equivalents. The reaction temperature is preferably from -50°C to the boiling point of the solvent, and more preferably from room temperature to 130°C.

[0195] As for the polyetherification reaction (STEP1), there are the following methods: a method of feeding the derivative (X), the reagent (Y), and the catalyst all at once; a method of dropping the reagent (Y) or a solution obtained by dissolving the reagent (Y) in a reaction solvent in the presence of the derivative (X) and the catalyst; a method of dropping the derivative (X) or a solution obtained by dissolving the derivative (X) in a reaction solvent in the presence of the reagent (Y) and the catalyst. After the polyetherification reaction is terminated, the etherification of STEP2 may be continuously performed by dropping the reagent (Z) or a solution obtained by dissolving the reagent (Z) in a reaction solvent. However, in order to remove the unreacted raw materials and catalysts in the system, the following methods may be flexibly used according to the raw materials used, the amount and properties of the reaction product obtained, and the following methods: a method of raising the temperature of the reactor to 130 to 230°C and removing the volatile components at about 1 to 50 mmHg; a method of adding an appropriate poor solvent or water to precipitate the polymer; a fractionation method, etc. Furthermore, a step of dissolving the obtained polyether compound in an appropriate solvent such as methyl isobutyl ketone or ethyl acetate and washing with water may be added.

[0196] The etherification after the polyetherification (STEP 2) can be carried out, for example, without a solvent or using a base as a catalyst in a solvent, at room temperature or, if necessary, under cooling or heating. As the solvent used in STEP 2, there can be exemplified alcohols such as methanol, ethanol, isopropanol, butanol, ethylene glycol, propylene glycol, diethylene glycol, glycerol, methyl cellosolve, ethyl cellosolve, butyl cellosolve, propylene glycol monomethyl ether, etc., ethers such as diethyl ether, dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, 1,4-dioxane, etc., chlorine-based solvents such as dichloromethane, chloroform, dichloroethane, trichloroethylene, etc., hydrocarbons such as hexane, heptane, benzene, toluene, xylene, cumene, nitriles such as acetonitrile, ketones such as acetone, ethyl methyl ketone, isobutyl methyl ketone, etc., esters such as ethyl acetate, n-butyl acetate, propylene glycol methyl ether acetate, lactones such as γ-butyrolactone, and aprotic polar solvents such as dimethyl sulfoxide, N,N-dimethylformamide, hexamethylphosphoramide, and N-methylpyrrolidone. As the solvent, one of these may be used alone, or two or more of these may be used in mixture. These solvents may be used in an amount within a range of 0 to 2,000 parts by mass based on 100 parts by mass of the reaction raw materials.

[0197] As for the base catalyst used in STEP2, there can be exemplified inorganic bases such as sodium hydroxide, potassium hydroxide, barium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, lithium hydride, sodium hydride, potassium hydride, calcium hydride, etc., alkyl metals such as methyl lithium, n-butyl lithium, methyl magnesium chloride, ethyl magnesium bromide, etc., alkoxides such as sodium methoxide, sodium ethoxide, potassium tert-butoxide, triethylamine, diisopropylethylamine, N,N-dimethylaniline, pyridine, 4-dimethylaminopyridine, etc. Organic bases. The amount used is preferably 0.1 to 1.5 equivalents relative to the amount of hydroxyl groups contained in the raw materials, and more preferably in the range of 1.0 to 1.2 equivalents. The reaction temperature is preferably -50°C to the boiling point of the solvent, and more preferably room temperature to 130°C.

[0198] As for the reaction method, the polyether compound may be prepared by feeding the reagent (Z) and the catalyst at once; by dripping the reagent (Z) or dissolving the reagent (Z) in a reaction solvent in the presence of the polyether compound and the catalyst; or by dripping a solution prepared by dissolving the polyether compound in a reaction solvent in the presence of the reagent (Z) and the catalyst. In this case, the amount of the reagent (Z) used is preferably 1.0 to 1.2 equivalents, more preferably 1.0 to 1.05 equivalents, relative to the amount of hydroxyl residues in the polyether compound. When using a plurality of reagents (Z), the following methods can be selected: a method in which a reagent (Z) with a large steric hindrance and low reactivity at the reaction site such as bromomethylcyclohexane is first added dropwise and aged, and then a reagent (Z) with a small steric hindrance and high reactivity at the reaction site such as propargyl bromide is added; a method in which a high boiling point reagent (Z) such as methanesulfonyl and p-toluenesulfonyl which cannot be removed under reduced pressure after the reaction is first added dropwise and aged, and then a low boiling point reagent (Z) such as propargyl bromide and propylene bromide which can be removed under reduced pressure after the reaction is added dropwise in a slightly excessive amount to increase the substitution rate. After the etherification is terminated, in order to remove unreacted raw materials, catalysts, etc. present in the system, there are methods of increasing the temperature of the reactor to 130 to 230° C. and removing volatile components under conditions of about 1 to 50 mmHg; a method of adding an appropriate poor solvent or water to precipitate the polymer; a method of performing classification, etc.; treatments can be flexibly selected according to the raw materials used and the properties of the reaction product obtained. Furthermore, at the end, the obtained polyether compound (A) may be dissolved in a suitable solvent such as methyl isobutyl ketone or ethyl acetate, and acid-washed with an aqueous solution of a suitable acid such as nitric acid or hydrochloric acid, followed by washing with ultrapure water to remove metal species such as sodium and potassium.

[0199] The polystyrene-equivalent weight average molecular weight Mw obtained by gel permeation chromatography of the polyether compound (A) obtained by the above-mentioned synthesis method is preferably 2,000 to 12,000, more preferably 2,000 to 8,000, from the viewpoint of landfilling properties and sublimation suppression.

[0200] When the weight average molecular weight Mw of the polyether compound (A) is 2000 to 12000, the amount of low molecular weight components that sublimate during baking is reduced, and the underlying film does not impair the embedding property. When the weight average molecular weight Mw is 2000 to 8000, the effect is further enhanced.

[0201] <(B) Organic Solvent>

[0202] Furthermore, the (B) organic solvent that can be used is not particularly limited as long as it can dissolve the above-mentioned (A) polyether compound and the (C) surfactant, (D) crosslinking agent, (E) thermally decomposable resin, (F) acid generator, and other additives described later.

[0203] Specifically, an organic solvent described in paragraphs

[0091] to

[0092] of Japanese Patent Application Laid-Open No. 2007-199653 may be added. More specifically, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, 2-heptanone, cyclopentanone, cyclohexanone and γ-butyrolactone, or a mixture containing one or more of these may be preferably used.

[0204] The amount of the organic solvent to be added is preferably in the range of 200 to 10,000 parts, more preferably 250 to 5,000 parts, based on 100 parts by mass of the (A) polyether compound.

[0205] In the resist underlayer film forming composition of the present invention, the aforementioned (B) organic solvent may be used in the form of a mixture of one or more organic solvents having a boiling point of less than 180°C ((B1) low boiling point solvent) and one or more organic solvents having a boiling point of more than 180°C ((B2) high boiling point solvent).

[0206] The high boiling point solvent is not particularly limited to hydrocarbons, alcohols, ketones, esters, ethers, chlorine-based solvents, etc. as long as it can dissolve the components of the resist underlayer film forming composition of the present invention. Specific examples thereof include 1-octanol, 2-ethylhexanol, 1-nonanol, 1-decanol, 1-undecanol, ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, 2,4-heptanediol, and the like. Alcohol, 2-ethyl-1,3-hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, glycerol, n-nonyl acetate, monohexyl ether, ethylene glycol mono-2-ethylhexyl ether, ethylene glycol monophenyl ether, ethylene glycol monobenzyl ether, diethylene glycol monoethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol monoisobutyl ether, diethylene glycol monohexyl ether, diethylene glycol monophenyl ether, diethylene glycol monobenzyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, Triethylene glycol dimethyl ether, triethylene glycol monomethyl ether, triethylene glycol-n-butyl ether, triethylene glycol butyl methyl ether, tetraethylene glycol dimethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, tripropylene glycol mono-n-propyl ether, tripropylene glycol mono-n-butyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, triacetic acid glycerol Oil esters, propylene glycol diacetate, dipropylene glycol methyl-n-propyl ether, dipropylene glycol methyl ether acetate, 1,4-butanediol diacetate, 1,3-butanediol diacetate, 1,6-hexanediol diacetate, triethylene glycol diacetate, γ-butyrolactone, methyl benzoate, ethyl benzoate, propyl benzoate, butyl benzoate, dihexyl malonate, diethyl succinate, dipropyl succinate, dibutyl succinate, dihexyl succinate, dimethyl adipate, diethyl adipate, dibutyl adipate, etc. As for the high boiling point solvent (B2), these may be used alone or in combination.

[0207] The high boiling point solvent can be appropriately selected from, for example, the above-mentioned ones according to the temperature at which the resist lower film forming composition of the present invention is subjected to heat treatment. The boiling point of the high boiling point solvent is preferably 180°C to 300°C, and more preferably 200°C to 300°C. It is believed that if this boiling point is used, there will be no risk of volatilization becoming too fast during baking (heat treatment), so sufficient thermal fluidity can be obtained during film formation, and a resist lower film with excellent embedding and planarization characteristics can be formed. In addition, if this boiling point is used, it will not remain in the film without volatilization after baking, so there will be no risk of adversely affecting the physical properties of the film such as embedding characteristics.

[0208] When a high boiling point solvent is used, the blending amount is preferably set to 1 to 30 parts by mass relative to 100 parts by mass of the organic solvent having a boiling point of less than 180° C. Such a blending amount is preferred because it can provide sufficient thermal fluidity during baking, does not remain in the film, and does not contribute to the deterioration of the film properties such as the landfill characteristics.

[0209] <Optional Ingredients>

[0210] The resist underlayer film-forming composition of the present invention may further contain an optional component other than the above-mentioned (A) polyether compound and the above-mentioned (B) organic solvent.

[0211] <(C) Surfactant>

[0212] The composition of the present invention may also contain (C) a surfactant. In the resist underlayer film forming composition of the present invention, a (C) surfactant may be added to improve the coating properties during spin coating. As for the surfactant, for example, those described in

[0142] to

[0147] in Japanese Patent Publication No. 2009-269953 may be used. The amount added when adding the surfactant is preferably 0.01 to 10 parts, more preferably 0.05 to 5 parts, relative to 100 parts by mass of the above-mentioned (A) reactant.

[0213] [(D) Cross-linking agent]

[0214] The resist underlayer film-forming composition of the present invention may further contain (D) a cross-linking agent.

[0215] The crosslinking agent (D) promotes crosslinking within the film, and because of its structure containing an aromatic ring, it is closely adjacent to the polyether compound (A), which has the effect of increasing the film density. Therefore, there are fewer holes such as solvent impregnation, and the swelling of the film after reprocessing is suppressed. Therefore, the crosslinking agent can be added as a crosslinking accelerator, a processing resistance improver, and a film swelling inhibitor.

[0216] As for the crosslinking agent (D), there is no particular limitation, and various well-known crosslinking agents can be widely used. For example, melamine crosslinking agents, acrylate crosslinking agents, glycoluril crosslinking agents, benzoguanamine crosslinking agents, urea crosslinking agents, β-hydroxyalkylamide crosslinking agents, isocyanurate crosslinking agents, aziridine crosslinking agents, oxazoline crosslinking agents, epoxy crosslinking agents, phenol crosslinking agents (such as hydroxymethyl or alkoxymethyl crosslinking agents of polynuclear phenols) can be exemplified. The content of the aforementioned (D) crosslinking agent is preferably 5 to 50 parts by mass, and more preferably 10 to 40 parts by mass, relative to 100 parts by mass of the aforementioned (A) polyether compound.

[0217] Specific examples of the melamine-based crosslinking agent include hexamethoxymethylated melamine, hexabutoxymethylated melamine, alkoxy and / or hydroxyl-substituted melamines thereof, and partial self-condensates thereof.

[0218] Specific examples of the acrylate crosslinking agent include dipentatriol hexaacrylate.

[0219] Specific examples of glycoluril-based crosslinking agents include tetramethoxymethyl glycoluril, tetrabutoxymethyl glycoluril, alkoxy and / or hydroxyl-substituted products thereof, and partial self-condensation products thereof.

[0220] Specific examples of the benzoguanamine-based crosslinking agent include tetramethoxymethylated benzoguanamine, tetrabutoxymethylated benzoguanamine, alkoxy and / or hydroxyl-substituted products thereof, and partial self-condensed products thereof.

[0221] Specific examples of the urea crosslinking agent include dimethoxymethylated dimethoxyethylene urea, alkoxy and / or hydroxyl-substituted products thereof, and partial self-condensates thereof.

[0222] Specific examples of the β-hydroxyalkylamide crosslinking agent include N,N,N′,N′-tetrakis(2-hydroxyethyl)adipamide.

[0223] Specific examples of the isocyanurate-based crosslinking agent include triglycidyl isocyanurate and triallyl isocyanurate.

[0224] Specific examples of the aziridine crosslinking agent include 4,4′-bis(ethyleneiminocarbonylamino)diphenylmethane and 2,2-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate].

[0225] Specific examples of the oxazoline crosslinking agent include 2,2'-isopropylidenebis(4-benzyl-2-oxazoline), 2,2'-isopropylidenebis(4-phenyl-2-oxazoline), 2,2'-isopropylidenebis(4-phenyl-2-oxazoline), 2,2'-methylenebis-4,5-diphenyl-2-oxazoline, 2,2'-methylenebis-4-phenyl-2-oxazoline, 2,2'-methylenebis-4-tert-butyl-2-oxazoline, 2,2'-bis(2-oxazoline), 1,3-phenylenebis(2-oxazoline), 1,4-phenylenebis(2-oxazoline), and 2-isopropenyloxazoline copolymers.

[0226] Specific examples of epoxy crosslinking agents include diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, poly(glycidyl methacrylate), trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol tetraglycidyl ether.

[0227] Specific examples of the polynuclear phenol crosslinking agent include compounds represented by the following general formula (XL-1).

[0228] [Chemistry 23]

[0229]

[0230] In the formula, L is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. R4 is a hydrogen atom or an alkyl group having 1 to 20 carbon atoms. q is an integer of 1 to 5.

[0231] L is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. Q is an integer of 1 to 5, preferably 2 or 3. Specifically, L includes groups obtained by removing q hydrogen atoms from methane, ethane, propane, butane, isobutane, pentane, cyclopentane, hexane, cyclohexane, methylpentane, methylcyclohexane, dimethylcyclohexane, trimethylcyclohexane, benzene, toluene, xylene, ethylbenzene, ethylisopropylbenzene, diisopropylbenzene, methylnaphthalene, ethylnaphthalene, and eicosane. R4 is a hydrogen atom or an alkyl group having 1 to 20 carbon atoms. Specifically, alkyl groups having 1 to 20 carbon atoms include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, pentyl, isopentyl, hexyl, octyl, ethylhexyl, decyl, and eicosane, and preferably a hydrogen atom or a methyl group.

[0232] As for the examples of the compounds represented by the general formula (XL-1), the following compounds can be specifically exemplified. Among them, hexamethoxymethylated forms of trisphenolmethane, trisphenolethane, 1,1,1-tris(4-hydroxyphenyl)ethane, and tris(4-hydroxyphenyl)-1-ethyl-4-isopropylbenzene are particularly preferred from the viewpoint of improving the hardening property and film thickness uniformity of the organic film. R4 is the same as described above.

[0233] [Chemistry 24]

[0234]

[0235] [Chemistry 25]

[0236]

[0237] <(E) Thermally Decomposable Resin>

[0238] Furthermore, the resist underlayer film-forming composition of the present invention may contain (E) a pyrolyzable resin from the viewpoint of reducing the film density. By containing (E) a pyrolyzable resin, since the pyrolyzable resin decomposes during baking and sublimates from the film, minute pores can be formed in the film. Therefore, the swelling of the film after reworking becomes larger, so the porosity of the film can be increased.

[0239] As the (E) pyrolyzable resin, for example, a liquid additive having a polyethylene glycol or polypropylene glycol structure, or a pyrolyzable polymer (resin) having a weight loss rate of 40% by mass or more between 30°C and 250°C and a weight average molecular weight of 300 to 200,000 can be preferably used. The pyrolyzable polymer preferably contains a repeating unit having an acetal structure represented by any of the following general formulae (DP1), (DP1a) to (DP3a).

[0240] [Chemistry 26]

[0241]

[0242] In the formula, R 1 is a hydrogen atom or an optionally substituted saturated or unsaturated monovalent organic group having 1 to 30 carbon atoms. W is a saturated or unsaturated divalent organic group having 2 to 30 carbon atoms.

[0243] [Chemistry 27]

[0244]

[0245] In formulas (DP1a) to (DP3a), R 1a W is an alkyl group having 1 to 4 carbon atoms. a It is a saturated or unsaturated divalent hydrocarbon group having 4 to 10 carbon atoms, and may have an ether bond. b1 Each independently is -W a -OH, or an optionally substituted saturated or unsaturated monovalent organic group having 1 to 30 carbon atoms; 1c R is a hydrogen atom, or an optionally substituted aryl group having 6 to 20 carbon atoms, or a heteroaryl group having 4 to 20 carbon atoms. c1 are each independently an alkyl group having 1 to 4 carbon atoms, or -W a -OH. n represents the average number of repeating units, which is 3 to 500.

[0246] Specific examples of the thermally decomposable resin include those shown below, but are not limited to these.

[0247] [Chemistry 28]

[0248]

[0249] [Chemistry 29]

[0250]

[0251] [Chemistry 30]

[0252]

[0253] [Chemistry 31]

[0254]

[0255] n represents an average repeating unit, and is 3 or more and 500 or less.

[0256] The amount of the (E) thermally decomposable resin added is preferably 0.05 to 50 parts, more preferably 0.1 to 10 parts, based on 100 parts by mass of the (A) polyether compound.

[0257] <(F) Acid Generator>

[0258] In order to further promote the curing reaction of the polyether compound (A) mentioned above, an acid generator may be added to the resist underlayer film forming composition of the present invention. Acid generators may generate acid by thermal decomposition (thermal acid generators) or by light irradiation (photoacid generators), and both may be added. Specifically, materials described in paragraphs

[0061] to

[0085] of Japanese Patent Publication No. 2007-199653 may be added, but are not limited to these.

[0259] The acid generator may be used alone or in combination of two or more. The amount of the acid generator added is preferably 0.05 to 50 parts, more preferably 0.1 to 10 parts, based on 100 parts by mass of the polyether compound (A).

[0260] [Physical properties related to film density]

[0261] The composition for forming an anti-etching underlayer film of the present invention, for example, when the composition for forming an anti-etching underlayer film of the present invention is applied to a substrate to obtain a coating film, the coating film is subjected to firing at 180°C for 60 seconds, and then subjected to additional firing at 350°C for 60 seconds, the film thickness of which is defined as FT-1, and when, after the additional firing, an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is arranged on the coating film, the film is then allowed to stand for 30 seconds, the coating film is spin-dried, and then the coating film is baked at 100°C for 60 seconds to evaporate the OK73 diluent, and the film thickness of the coating film is defined as FT-2, it is ideal that 101<{(FT-2) / (FT-1)}×100.

[0262] If 101<{(FT-2) / (FT-1)}×100, it means that the film immediately after firing will be a porous film with a large number of pores such as the OK73 diluent can penetrate, and the larger the value, the more porous and low-density the film. Therefore, considering the air permeability, 101<{(FT-2) / (FT-1)}×100 is more ideal, and 101.5<{(FT-2) / (FT-1)}×100 is even more ideal.

[0263] When the crosslinking agent (D) is further included, the composition is preferably 100<{(FT-2) / (FT-1)}×100<103. As previously mentioned, the crosslinking agent (D) has the effect of increasing the density of the membrane. Therefore, there are fewer holes such as those impregnated with the solvent, and the swelling of the membrane after reworking is suppressed. Therefore, the crosslinking agent can be added as a crosslinking accelerator and a swelling inhibitor of the membrane.

[0264] When (E) a pyrolyzable resin is further included, the composition is preferably 101.5 < {(FT-2) / (FT-1)} × 100. By including (E) a pyrolyzable resin, the pyrolyzable resin decomposes during baking and sublimates from the film, thereby forming minute pores in the film. Therefore, the swelling of the film after reworking increases, thereby increasing the porosity of the film and reducing the film density.

[0265] When both (D) a crosslinking agent and (E) a thermally decomposable resin are further included, it is also preferable that the ratio is 100<{(FT-2) / (FT-1)}×100.

[0266] (D) Crosslinking agent and (E) thermally decomposable resin have opposite effects as density adjusters of the film, so when both are contained at the same time, as long as the curing of the film can be confirmed, when comparing the difference in film thickness before and after reworking, it is sufficient to achieve (FT-2)>(FT-1).

[0267] Hereinafter, a method for producing a resist underlayer film, a method for forming a pattern, and a method for producing a semiconductor device using the resist underlayer film-forming composition of the present invention will be described.

[0268] [Method for producing resist underlayer film]

[0269] The method for manufacturing the resist underlayer film of the present invention comprises the following steps:

[0270] The resist underlayer film forming composition of the present invention is applied on a semiconductor substrate to obtain a coating film,

[0271] The coated film is fired to obtain a resist underlayer film.

[0272] Semiconductor substrates, such as substrates used in the manufacture of semiconductor devices, such as silicon wafer substrates, silicon / silicon dioxide coated substrates, silicon nitride substrates, glass substrates, ITO substrates, polyimide substrates, and low dielectric constant material (low-k material) coated substrates.

[0273] The resist underlayer film forming composition of the present invention is applied onto the semiconductor substrate by an appropriate coating method such as a spinner or a coater to obtain a coating film.

[0274] Thereafter, the coating film is fired to form a resist underlayer film.

[0275] As for the firing conditions, it can be appropriately selected from the firing temperature of 80°C to 400°C and the firing time of 0.3 to 60 minutes. It is more ideal to have a firing temperature of 150°C to 350°C and a firing time of 0.5 to 2 minutes. It is more ideal to have a two-stage firing of firing at a firing temperature of 100°C to 200°C and 0.5 to 2 minutes, and then to have an additional firing at 200°C to 350°C and 0.5 to 2 minutes. Here, as for the film thickness of the formed lower film, for example, 10 to 1500nm, it is more ideal to have 500 to 1000nm. In addition, if a quartz substrate is used as a substrate, a replica of a quartz imprint mold (mold replication portion) can be made.

[0276] In addition, a close-contact layer and / or a polysilicon oxide layer containing less than 99% by mass or less than 50% by mass Si can be formed by coating or vapor deposition on the resist lower film formed as above. For example, the close-contact layer recorded in Japanese Unexamined Patent Publication No. 2013-202982 and Japanese Patent No. 5827180, except the method of forming the silicon-containing resist lower film (inorganic resist lower film) recorded in WO2009 / 104552A1 into a composition by spin coating, can be formed by the inorganic material film of Si system with CVD method etc.

[0277] Furthermore, the resist underlayer film forming composition of the present invention can form an underlayer film showing improved flatness as described above. For example, the resist underlayer film forming composition of the present invention is applied to a semiconductor substrate having a portion with a height difference and a portion without a height difference (so-called a height difference substrate) to obtain a coating film, and the coating film is fired to form a resist underlayer film in which the height difference between the portion with a height difference and the portion without a height difference falls within a range of 3 to 100 nm.

[0278] [Pattern Formation Method]

[0279] The pattern forming method of the present invention comprises the following steps:

[0280] forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition of the present invention,

[0281] forming a hardening composition film on the resist underlayer film,

[0282] The curable composition film is brought into contact with a mold,

[0283] The curable composition film is irradiated with light or electron beam to form a cured film.

[0284] The cured film is separated from the mold.

[0285] This pattern forming method is called an imprint method using a mold. The imprint method may also be a nanoimprint method. By using the pattern forming method using the imprint method of the present invention, it is possible to utilize a resist underlayer film that has good processing tolerance, excellent filling and flatness, low film density, and good air permeability. Therefore, by using the pattern forming method using the imprint method of the present invention, it is possible to quickly remove bubbles generated when the mold is pressed against the curable composition film, and to form a fine pattern.

[0286] Hereinafter, each step will be described in more detail.

[0287] <Step of Forming Resist Underlayer Film>

[0288] In this step, for example, a resist underlayer film can be formed on a semiconductor substrate from the resist underlayer film-forming composition of the present invention by the method for producing a resist underlayer film of the present invention described above.

[0289] <Step of Forming a Curable Composition Film>

[0290] This step is a step of forming a curable composition film on the resist underlayer film.

[0291] The composition of the curable composition film formed on the resist underlayer film is not particularly limited as long as it is photosensitized for use in exposure. Both negative photoresists and positive photoresists can be used. There are positive photoresists composed of novolac resin and 1,2-naphthoquinonediazide sulfonate, chemically amplified photoresists composed of a binder and a photoacid generator having a group that decomposes due to acid and increases the alkali dissolution rate, chemically amplified photoresists composed of a low molecular compound that decomposes due to acid and increases the alkali dissolution rate of the photoresist, an alkali-soluble binder, and a photoacid generator, and chemically amplified photoresists composed of a binder having a group that decomposes due to acid and increases the alkali dissolution rate, a low molecular compound that decomposes due to acid and increases the alkali dissolution rate of the photoresist, and a photoacid generator. Examples include APEX-E manufactured by Shipley, PAR710 manufactured by Sumitomo Chemical, and SEPR430 manufactured by Shin-Etsu Chemical. In addition, examples include fluorine-containing polymer photoresists described in Proc. SPIE, Vol. 3999, 330-334 (2000), Proc. SPIE, Vol. 3999, 357-364 (2000), and Proc. SPIE, Vol. 3999, 365-374 (2000).

[0292] [Method of using the curable composition]

[0293] As for the method of applying the curable composition, inkjet method, dip coating method, air knife coating method, curtain coating method, wire rod coating method, gravure coating method, extrusion coating method, spin coating method, slit scanning method, etc. can be used. In order to apply the curable composition in the form of droplets, the inkjet method is suitable, and in order to apply the curable composition, the spin coating method is suitable. In this step, a close contact layer and / or a polysilicon layer containing 99% by mass or less, or 50% by mass or less of Si can also be formed by coating or evaporation on the resist lower film for nanoimprinting, and the curable composition can be applied thereon.

[0294] In the step of forming the curable composition film, an adhesion layer and / or a polysilicon layer containing 99 mass % or less of Si may be formed on the resist underlayer film by coating or vapor deposition.

[0295] By forming the adhesion layer, the pattern peeling can be sufficiently suppressed in the subsequent step of separating the mold. In addition, by forming a polysilicon layer containing 99 mass % or less of Si, the optical properties of the film can be adjusted, and reflection control can be achieved.

[0296] <Step of bringing the curable composition film into contact with the mold>

[0297] In this step, the curable composition film is brought into contact with the mold. For example, if the liquid curable composition film is brought into contact with the mold having a prototype pattern for transferring the pattern shape, a liquid film is formed in which the curable composition fills the recessed parts of the fine pattern on the surface of the mold.

[0298] Considering the step of irradiating light or electron beams described later, it is recommended to use a mold with a light-transmitting material as the base material. Specifically, the mold base material is preferably glass, quartz, PMMA, light-transparent resins such as polycarbonate resin, transparent metal vapor-deposited films, soft films such as polydimethylsiloxane, light-curing films, metal films, etc. Quartz is the most ideal mold base material because it has a small thermal expansion coefficient and small pattern strain.

[0299] The fine pattern on the surface of the mold preferably has a pattern height of 4 nm or more and 200 nm or less. In order to improve the processing accuracy of the substrate, a certain degree of pattern height is necessary, but if the pattern height is low, the force required to peel the mold from the cured film in the step of separating the cured film from the mold described later is low, and the number of defects remaining on the mask side due to the shredding of the resist pattern is small. It is recommended to select and adopt an appropriately balanced pattern height in consideration of these.

[0300] In addition, due to the impact of stripping the mold, the elastic deformation of the resist pattern causes the adjacent resist patterns to contact each other, which may cause the resist pattern to stick or break. This can be avoided by setting the pattern height to less than about 2 times the pattern width (aspect ratio less than 2).

[0301] In order to improve the releasability of the curable composition from the surface of the mold, the mold may also be surface treated in advance. As for the surface treatment method, a method such as coating a release agent on the surface of the mold to form a release agent layer can be cited. As for the release agent, examples include silicone release agents, fluorine release agents, hydrocarbon release agents, polyethylene release agents, polypropylene release agents, paraffin release agents, lignite release agents, palm release agents, etc. are listed. Fluorine and hydrocarbon release agents are more ideal. As for commercial products, for example, there are OPTOOL (registered trademark) DSX made by Daikin Industries (stock). A release agent can be used alone, or two or more can be used in combination.

[0302] In this step, when the mold is brought into contact with the curable composition, the pressure applied to the curable composition is not particularly limited. A pressure of 0 MPa or more and 100 MPa or less is recommended. The pressure is preferably 0 MPa or more and 50 MPa or less, 30 MPa or less, or 20 MPa or less.

[0303] When the liquid droplets of the curable composition are pre-applied in the previous step (the step of applying the curable composition), the application of the curable composition in this step is quickly completed. As a result, the contact time between the mold and the curable composition can be shortened. The contact time is not particularly limited, but is preferably 0.1 seconds or more and 600 seconds or less, 3 seconds or less, or 1 second or less. If the contact time is too short, the application and filling are insufficient, and there is a risk of a defect called an unfilled defect.

[0304] This step can be performed under any of the following conditions: atmospheric gas environment, reduced pressure gas environment, and inert gas environment. It is preferably performed under a pressure of 0.0001 atmospheres or more and 10 atmospheres or less. In order to prevent the influence of oxygen and moisture on the curing reaction, it is recommended to perform the step under a reduced pressure gas environment or an inert gas environment. Specific examples of inert gases that can be used to create an inert gas environment include nitrogen, carbon dioxide, helium, argon, CFC, HCFC, HFC, or a mixture thereof.

[0305] This step can also be performed in a gas environment containing condensable gas (hereinafter referred to as "condensable gas environment"). The so-called condensable gas in this specification refers to a gas that will condense and liquefy due to the capillary pressure generated during filling when it is filled in the recesses of the fine pattern formed on the mold and the gap between the mold and the substrate together with the curable composition. In addition, the condensable gas exists in the form of gas in the gas environment before the curable composition contacts the mold in this step. If this step is performed in a condensable gas environment, the gas filled in the recesses of the fine pattern will be liquefied by the capillary pressure generated by the curable composition, thereby eliminating bubbles, so the filling property is excellent. Condensable gas can also be dissolved in the curable composition.

[0306] The boiling point of the condensable gas is not limited as long as it is lower than the gas environment temperature in this step, but is preferably -10°C or higher, or +10°C or higher and +23°C or lower.

[0307] The vapor pressure of the condensable gas at the gas atmosphere temperature in this step is not particularly limited as long as it is equal to or lower than the mold pressure, but is preferably in the range of 0.1 MPa to 0.4 MPa.

[0308] Specific examples of condensable gases include chlorofluorocarbons (CFCs) such as trichlorofluoromethane, fluorocarbons (FCs), hydrochlorofluorocarbons (HCFCs), hydrofluorocarbons (HFCs) such as 1,1,1,3,3-pentafluoropropane (CHF2CH2CF3, HFC-245fa, PFP), and hydrofluoroethers (HFEs) such as pentafluoroethyl methyl ether (CF3CF2OCH3, HFE-245mc).

[0309] The condensable gas may be used alone or in a mixture of two or more. These condensable gases may also be mixed with non-condensable gases such as air, nitrogen, carbon dioxide, helium, and argon. As for the non-condensable gas mixed with the condensable gas, air and helium are more preferable.

[0310] <Step of irradiating the curable composition film with light or electron beam to form a cured film>

[0311] In this step, the curable composition film is irradiated with light or electron beams to form a cured film. That is, the curable composition film filled in the fine pattern of the mold is irradiated with light or electron beams through the mold, and the curable composition filled in the fine pattern of the mold is directly cured in this state, thereby forming a cured film having a pattern shape.

[0312] Light or electron beam is selected according to the sensitivity wavelength of the curable composition. Specifically, ultraviolet light, X-rays, electron beams, etc. with a wavelength of more than 150nm and less than 400nm can be appropriately selected and used. As for the light source of light or electron beam, high-pressure mercury lamps, ultra-high-pressure mercury lamps, low-pressure mercury lamps, Deep-UV lamps, carbon arc lamps, chemical lamps, metal halide lamps, xenon lamps, KrF excimer lasers, ArF excimer lasers, F2 excimer lasers, etc. can be listed. The number of light sources can be 1 or plural. Irradiation can be performed on the entire curable composition filled in the fine pattern of the mold, or it can be performed only on a part of the area. Light irradiation can be performed intermittently multiple times on all areas on the substrate, or it can be continuously irradiated on all areas. In addition, a part of the area on the substrate can be irradiated for the first time, and then a second irradiation can be performed on a different area from the area.

[0313] The cured film obtained in this manner preferably has a pattern having a size of 1 nm or more, or 10 nm or more, and 10 mm or less, or 100 μm or less.

[0314] <Steps for separating the cured film from the mold>

[0315] In this step, the cured film is separated from the mold. By pulling the cured film having the pattern shape away from the mold, a cured film having a pattern shape that is a reverse pattern of the fine pattern formed on the mold can be obtained in a self-supporting state.

[0316] As for the method of separating the cured film having a pattern shape from the mold, if it is a means to move the cured film and the mold in a direction of relative separation, there is no particular limitation as long as a part of the cured film having a pattern shape is not physically damaged, and there is no particular limitation on various conditions. For example, the substrate may be fixed and the mold may be moved away from the substrate to be peeled off, or the mold may be fixed and the substrate may be moved away from the mold to be peeled off. Alternatively, the substrate and the mold may be pulled apart and moved in opposite directions to be peeled off.

[0317] In addition, when the step of bringing the curable composition into contact with the mold is performed under a condensable gas environment, when the cured film is separated from the mold in this step, the condensable gas is vaporized as the pressure at the interface between the cured film and the mold decreases. This can reduce the demolding force, which is the force required to separate the cured film from the mold.

[0318] By the above steps, a cured film having a desired concavo-convex pattern shape derived from the concavo-convex shape of the mold at a desired position can be prepared.

[0319] In addition, the pattern forming method using the imprint method has been described above, but the resist underlayer film obtained by the resist underlayer film forming composition of the present invention is not limited to the pattern forming method using the imprint method. For example, it can also be used as a resist underlayer film in a pattern forming method for a multilayer resist process.

[0320] [Method for manufacturing semiconductor device]

[0321] A method for manufacturing a semiconductor device according to a first aspect of the present invention comprises the following steps:

[0322] forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition of the present invention,

[0323] forming a resist film on the resist underlayer film,

[0324] The resist film is irradiated with light or electron beams and then developed to form a resist pattern.

[0325] Using the formed resist pattern as a mask, the resist underlayer film is etched to obtain a patterned underlayer film,

[0326] The semiconductor substrate is processed using the patterned underlying film as a mask.

[0327] Furthermore, a method for manufacturing a semiconductor device according to a second aspect of the present invention comprises the following steps:

[0328] forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition of the present invention,

[0329] forming a hard mask on the resist underlayer film,

[0330] Then, a resist film is formed on the hard mask film.

[0331] The resist film is irradiated with light or electron beams and then developed to form a resist pattern.

[0332] The hard mask is etched using the formed resist pattern as a mask to obtain a patterned hard mask,

[0333] Using the patterned hard mask film as a mask, the lower layer film is etched to obtain a patterned resist lower layer film,

[0334] The semiconductor substrate is processed using the patterned resist underlayer film as a mask.

[0335] Hereinafter, the method for manufacturing a semiconductor device according to the first aspect and the method for manufacturing a semiconductor manufacturing apparatus according to the second aspect will be described in detail in sequence.

[0336] <First Aspect>

[0337] [Step of forming a resist underlayer film on a semiconductor substrate from the resist underlayer film-forming composition of the present invention]

[0338] In this step, for example, the resist underlayer film can be formed by the method for producing a resist underlayer film of the present invention described above.

[0339] [Step of forming a resist film on the resist underlayer film]

[0340] Next, a step of forming a resist film on the resist underlayer film is performed.

[0341] The material of the resist film is not particularly limited as long as it is a resist material that can be used in the multilayer resist method.

[0342] [Step of irradiating the resist film with light or electron beams and then developing the resist film to form a resist pattern]

[0343] Next, the resist film formed in the above manner is irradiated with light or electron beams and then developed to form a resist pattern.

[0344] The light or electron beam irradiated can be appropriately selected according to the characteristics of the resist film. The method of development is not particularly limited as long as it can be used in the multilayer resist method.

[0345] [Step of etching the resist underlayer film using the formed resist pattern as a mask to obtain a patterned underlayer film]

[0346] Next, the resist underlayer film is etched using the previously formed resist pattern as a protective film.

[0347] The etching in this step is preferably performed under conditions that make it easier to etch the resist underlayer film than the resist film. For example, when the resist film contains a large amount of silicon atoms, the resist film is not easily removed in the dry etching performed with an oxygen-based gas, and the resist underlayer film is etched preferentially, so it is more ideal to perform the dry etching with an oxygen-based gas.

[0348] Through this step, a patterned lower layer film can be obtained.

[0349] [Step of processing the semiconductor substrate using the patterned lower layer film as a mask]

[0350] Next, a step of processing the semiconductor substrate using the patterned lower layer film as a mask is performed.

[0351] Semiconductor substrate processing is preferably performed by dry etching using a fluorine-based gas.

[0352] Examples of fluorine-based gases include tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, and difluoromethane (CH2F2).

[0353] <Second Aspect>

[0354] The second aspect is different from the first aspect in the steps of forming a hard mask on the resist underlayer film, etching the hard mask using the resist pattern as a mask, and etching the resist underlayer film using the patterned hard mask. The second aspect will be described below, centering on the differences from the first aspect.

[0355] The material of the hard mask is not particularly limited as long as it is a material of the hard mask that can be used in a multilayer resist process.

[0356] In the etching of the inorganic hard mask, for example, dry etching can be used. In the dry etching of the inorganic hard mask, for example, tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, carbon monoxide, argon, oxygen, nitrogen, sulfur hexafluoride, difluoromethane, nitrogen trifluoride and chlorine trifluoride, chlorine, trichloroborane and dichloroborane can be used. It is ideal to use halogen gas in the dry etching of the inorganic hard mask, and it is more ideal to use fluorine gas. As for fluorine gas, tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, and difluoromethane (CH2F2) can be listed.

[0357] As in the second aspect, in the present invention, after forming a resist underlayer film on a substrate, a hard mask film is formed thereon, and then a resist film is coated thereon, whereby the pattern width of the resist film becomes narrower, and even when the resist film is coated thinly to prevent pattern collapse, the substrate can still be processed by selecting an appropriate etching gas. For example, a fluorine-based gas having a very fast etching rate for the resist film can be used as an etching gas to process the hard mask, a fluorine-based gas having a very fast etching rate for the hard mask can be used as an etching gas to process the resist underlayer film, and an oxygen-based gas having a very fast etching rate for the resist underlayer film can be used as an etching gas to process the substrate.

[0358] In any of the first and second aspects, an organic anti-reflection film may be formed on the upper layer of the resist underlayer film before forming the resist film or the hard mask. There is no particular limitation on the anti-reflection film composition used, and any composition conventionally used in the photolithography process may be selected and used. The anti-reflection film may be formed by conventional methods such as coating and firing using a spinner or a coater.

[0359] The resist underlayer film formed by the resist underlayer film forming composition of the present invention may absorb the light depending on the wavelength of the light used in the photolithography process. In addition, at this time, it can function as an anti-reflection film having the effect of preventing the reflected light from the substrate. Then, the underlayer film formed by the resist underlayer film forming composition of the present invention can function as a hard mask in the first embodiment. The underlayer film of the present invention can also be used as: a layer for preventing the interaction between the substrate and the resist film, a layer having the function of preventing the material used in the resist film or the substance generated during the exposure of the resist film from having a bad influence on the substrate, a layer having the function of preventing the diffusion of the substance generated from the substrate to the resist film during heating and firing, and a barrier layer for reducing the poisoning effect of the resist film caused by the dielectric layer of the semiconductor substrate, etc.

[0360] Furthermore, the underlayer film formed by the resist underlayer film forming composition of the present invention can be used as a filling material capable of filling the via hole without gaps in a substrate formed with via holes used in a dual metal damascene process, and can also be used as a planarizing material for planarizing the surface of a semiconductor substrate having irregularities.

[0361] As described above, the resist underlayer film forming composition of the present invention can realize a resist underlayer film having excellent embedding properties and flatness and exhibiting hardness that can withstand processing. Therefore, the resist underlayer film forming composition of the present invention is very useful even in the manufacturing method of a semiconductor device including pattern formation by a multilayer resist method as described above.

[0362] [Example]

[0363] Hereinafter, synthesis examples, comparative synthesis examples, embodiments, and comparative examples are shown to more specifically illustrate the present invention, but the present invention is not limited thereto. In addition, as for molecular weight, the weight average molecular weight (Mw) calculated as polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran as an eluent is obtained.

[0364] [Synthesis Examples and Comparative Synthesis Examples]

[0365] In the following synthesis examples and comparative synthesis examples, the aromatic compound group Ar1 shown below: any one of (Ar1-1) to (Ar1-8), the polyetherifying agent group: any one of (G1) to (G5), and the etherifying agent group: any one of (R1-1) to (R1-8) are used. The respective raw material groups are shown below.

[0366] [Chemistry 32]

[0367]

[0368] [Chemistry 33]

[0369]

[0370] [Chemistry 34]

[0371]

[0372] Ms represents methanesulfonyl.

[0373] [Synthesis Example 1] Synthesis of Resist Underlayer Film-Forming Compound (A-1)

[0374] 10.0 g of an aromatic compound (Ar1-1), 13.2 g of a polyetherifying agent (G3), 16.7 g of potassium carbonate, and 30 g of N,N-dimethylformamide (DMF) were mixed, and the mixture was stirred at 120°C for 6 hours. Thereafter, the temperature of the mixture was lowered to 90°C, and a solution of 4.6 g of an etherifying agent (R1-1) and 10.0 g of DMF were added dropwise to the mixture, and the mixture was stirred for another 16 hours. After the reaction, the mixture was returned to room temperature, dissolved in 150 ml of methyl isobutyl ketone (MIBK), washed twice with 100 ml of ultrapure water, then washed with 100 ml of a 3% nitric acid aqueous solution, and then washed four times with 100 ml of ultrapure water. Then, the solvent was removed under reduced pressure, 200 g of propylene glycol monomethyl ether acetate (PGMEA) was added to the residue, and the solvent was removed under reduced pressure, thereby performing PGMEA replacement. Thereby, a PGMEA solution of the compound for forming a resist underlayer film (A-1) which is a polyether compound was obtained.

[0375] (A-1): Mw = 2198

[0376] [Chemistry 35]

[0377]

[0378] [Synthesis Example 2] Synthesis of Resist Underlayer Film-Forming Compound (A-2)

[0379] The aromatic compound (Ar1-1) of Synthesis Example 1 was changed to 10.0 g of the aromatic compound (Ar1-2), the amount of the polyetherizing agent (G3) was changed to 21.8 g, the amount of potassium carbonate was changed to 27.6 g, and the amount of the etherifying agent (R1-1) was changed to 7.5 g. In addition, a PGMEA solution of a compound (A-2) for forming an anti-etching agent underlayer film, which is a polyether compound, was obtained in the same manner as in Synthesis Example 1.

[0380] (A-2): Mw = 2439

[0381] [Chemistry 36]

[0382]

[0383] [Synthesis Example 3] Synthesis of Compound (A-3) for Forming Resist Underlayer Film

[0384] The aromatic compound (Ar1-1) of Synthesis Example 1 was changed to 10.0 g of the aromatic compound (Ar1-3), the amount of the polyetherizing agent (G3) was changed to 13.6 g, the amount of potassium carbonate was changed to 17.3 g, and the amount of the etherifying agent (R1-1) was changed to 4.7 g. In addition, a PGMEA solution of a compound (A-3) for forming an anti-etching agent underlayer film, which is a polyether compound, was obtained in the same manner as in Synthesis Example 1.

[0385] (A-3): Mw = 2615

[0386] [Chemistry 37]

[0387]

[0388] [Synthesis Example 4] Synthesis of Compound (A-4) for Forming Resist Underlayer Film

[0389] The aromatic compound (Ar1-1) of Synthesis Example 1 was changed to 10.0 g of the aromatic compound (Ar1-4), the amount of the polyetherizing agent (G3) was changed to 15.0 g, the amount of potassium carbonate was changed to 19.0 g, and the amount of the etherifying agent (R1-1) was changed to 5.2 g. In addition, a PGMEA solution of a compound (A-4) for forming an anti-etching agent underlayer film, which is a polyether compound, was obtained in the same manner as in Synthesis Example 1.

[0390] (A-4): Mw = 2320

[0391] [Chemistry 38]

[0392]

[0393] [Synthesis Example 5] Synthesis of Compound (A-5) for Forming Resist Underlayer Film

[0394] The aromatic compound (Ar1-1) of Synthesis Example 1 was changed to 10.0 g of aromatic compound (Ar1-5), the polyetherizing agent (G3) was changed to 7.6 g of polyetherizing agent (G1), the amount of potassium carbonate used was changed to 20.0 g, the etherifying agent (R1-1) was changed to 9.8 g of etherifying agent (R1-2), and the reaction temperature was changed to 60°C. Except for this, a PGMEA solution of a compound (A-5) for forming an anti-etching agent underlayer film which is a polyether compound was obtained in the same manner as in Synthesis Example 1.

[0395] (A-5): Mw = 5594

[0396] [Chemistry 39]

[0397]

[0398] [Synthesis Example 6] Synthesis of Compound (A-6) for Forming Resist Underlayer Film

[0399] 10.0 g of an aromatic compound (Ar1-6), 7.9 g of a polyetherifying agent (G3), 20.1 g of potassium carbonate, and 30 g of DMF are mixed, and the mixture is stirred at 120°C for 6 hours. Afterwards, the mixture is cooled to 90°C, 3.5 g of an etherifying agent (R1-3) is added, and the mixture is reacted for 6 hours. Afterwards, the reaction product is brought to 50°C and 8.9 g of an etherifying agent (R1-2) is added, and the mixture is reacted for 16 hours. The reaction product is returned to room temperature, washed with 300 ml of MIBK and 200 ml of water, and washed with 150 ml of a 3% nitric acid aqueous solution. Then, the reaction product is washed 4 times with 200 ml of water, and the solvent is removed under reduced pressure. Next, 300 g of PGMEA is added to the residue, and the solvent is removed under reduced pressure, thereby performing PGMEA substitution. In this way, a PGMEA solution of a compound (A-6) for forming an underlayer film of a resist, which is a polyether compound, is obtained.

[0400] (A-6): Mw = 6240

[0401] [Chemistry 40]

[0402]

[0403] [Synthesis Example 7] Synthesis of Compound (A-7) for Forming Resist Underlayer Film

[0404] 10.0 g of an aromatic compound (Ar1-7), 5.1 g of a polyetherifying agent (G1), 17.9 g of potassium carbonate, and 30 g of DMF were mixed, and the mixture was stirred at 80°C for 6 hours. After that, the temperature of the mixture was set to 90°C, 3.1 g of an etherifying agent (R1-3) was added thereto, and the mixture was reacted for 6 hours. Then, the temperature of the reaction product was set to 50°C, 7.9 g of an etherifying agent (R1-2) was added thereto, and the mixture was reacted for 16 hours. The reaction product was returned to room temperature, washed with 300 ml of MIBK and 200 ml of water, and washed with 150 ml of a 3% nitric acid aqueous solution. Then, the reaction product was washed 4 times with 200 ml of water, the solvent was removed under reduced pressure, 300 g of PGMEA was added to the residue, and the solvent was removed under reduced pressure, thereby performing PGMEA substitution. Thus, a PGMEA solution of a compound (A-7) for forming a resist underlayer film, which is a polyether compound, was obtained.

[0405] (A-7): Mw = 4425

[0406] [Chemistry 41]

[0407]

[0408] [Synthesis Example 8] Synthesis of Compound (A-8) for Forming Resist Underlayer Film

[0409] The polyetherizing agent (G1) in Synthesis Example 7 was changed to 5.0 g of polyetherizing agent (G2), the etherifying agent (R1-3) was changed to 3.5 g of etherifying agent (R1-4), and the etherifying agent (R1-2) was changed to 6.4 g of etherifying agent (R1-5). In the same manner as in Synthesis Example 7, a PGMEA solution of a compound (A-8) for forming an anti-etching agent underlayer film, which is a polyether compound, was obtained.

[0410] (A-8): Mw = 4400

[0411] [Chemistry 42]

[0412]

[0413] [Synthesis Example 9] Synthesis of Compound (A-9) for Forming Resist Underlayer Film

[0414] The etherifying agent (R1-4) in Synthesis Example 8 was changed to 3.1 g of etherifying agent (R1-3), and the etherifying agent (R1-5) was changed to 7.9 g of etherifying agent (R1-2). In the same manner as in Synthesis Example 8, a PGMEA solution of a compound (A-9) for forming an anti-etching agent underlayer film, which is a polyether compound, was obtained.

[0415] (A-9): Mw = 4515

[0416] [Chemistry 43]

[0417]

[0418] [Synthesis Example 10] Synthesis of Compound (A-10) for Forming Resist Underlayer Film

[0419] A PGMEA solution of a resist underlayer film-forming compound (A-10) which is a polyether compound was obtained in the same manner as in Synthesis Example 9, except that the etherifying agent (R1-3) in Synthesis Example 9 was changed to 2.9 g of the etherifying agent (R1-6).

[0420] (A-10): Mw = 4550

[0421] [Chemistry 44]

[0422]

[0423] [Synthesis Example 11] Synthesis of Compound (A-11) for Forming Resist Underlayer Film

[0424] 10.0 g of an aromatic compound (Ar1-7), 7.1 g of a polyetherifying agent (G3), 17.9 g of potassium carbonate, and 30 g of DMF were mixed, and the mixture was stirred at 120° C. for 6 hours. Then, the temperature of the mixture was set to 90° C., 3.1 g of an etherifying agent (R1-3) was added thereto, and the mixture was reacted for 6 hours. Then, the temperature of the reaction product was set to 50° C., 7.9 g of an etherifying agent (R1-2) was added thereto, and the mixture was reacted for 16 hours. The reaction product was returned to room temperature, washed with 300 ml of MIBK and 200 ml of water, and washed with 150 ml of a 3% nitric acid aqueous solution. Then, the reaction product was washed 4 times with 200 ml of water, the solvent was removed under reduced pressure, 300 g of PGMEA was added to the residue, and the solvent was removed under reduced pressure, thereby performing PGMEA substitution. In this way, a PGMEA solution of a compound (A-11) for forming a resist underlayer film, which is a polyether compound, was obtained.

[0425] (A-11): Mw = 4820

[0426] [Chemistry 45]

[0427]

[0428] [Synthesis Example 12] Synthesis of Compound (A-12) for Forming Resist Underlayer Film

[0429] The polyetherifying agent (G3) in Synthesis Example 11 was changed to 9.0 g of polyetherifying agent (G4), and the etherifying agent (R1-3) was changed to 3.9 g of etherifying agent (R1-8). In the same manner as in Synthesis Example 11, a PGMEA solution of a compound (A-12) for forming an anti-etching agent underlayer film, which is a polyether compound, was obtained.

[0430] (A-12): Mw = 4705

[0431] [Chemistry 46]

[0432]

[0433] [Synthesis Example 13] Synthesis of Compound (A-13) for Forming Resist Underlayer Film

[0434] The polyetherifying agent (G1) in Synthesis Example 11 was changed to 8.3 g of polyetherifying agent (G5), and the etherifying agent (R1-3) was changed to 3.4 g of etherifying agent (R1-7). In the same manner as in Synthesis Example 11, a PGMEA solution of a compound (A-13) for forming an anti-etching agent underlayer film, which is a polyether compound, was obtained.

[0435] (A-13): Mw = 4611

[0436] [Chemistry 47]

[0437]

[0438] [Synthesis Example 14] Synthesis of Compound (A-14) for Forming Resist Underlayer Film

[0439] The aromatic compound (Ar1-1) in Synthesis Example 1 was changed to 10.0 g of the aromatic compound (Ar1-8), the amount of the polyetherizing agent (G3) used was changed to 6.5 g, the amount of potassium carbonate used was changed to 8.3 g, and the amount of the etherifying agent (R1-2) used was changed to 2.0 g. In addition, a PGMEA solution of a compound (A-14) for forming an anti-etching agent underlayer film, which is a polyether compound, was obtained in the same manner as in Synthesis Example 1.

[0440] (A-14): Mw = 7100

[0441] [Chemistry 48]

[0442]

[0443] [Synthesis Example 15] Synthesis of Compound (A-15) for Forming Resist Underlayer Film

[0444] 5.0 g of aromatic compound (Ar1-2), 5.0 g of (Ar1-7), 14.4 g of polyetherifying agent (G3), 22.7 g of potassium carbonate, and 30 g of N,N-dimethylformamide (DMF) were mixed, and the mixture was stirred at 120°C for 6 hours. Then, the temperature was set to 90°C, and 2.4 g of etherifying agent (R1-3) was added, and the reaction was carried out for 6 hours. Then, the temperature was set to 50°C, and 4.9 g of etherifying agent (R1-2) was added, and the reaction was carried out for 16 hours. After the reaction, the mixture was returned to room temperature and dissolved in 150 ml of methyl isobutyl ketone (MIBK), and then washed twice with 100 ml of ultrapure water, then washed with 100 ml of 3% nitric acid aqueous solution, and then washed four times with 100 ml of ultrapure water. Then, the solvent was removed under reduced pressure, and 200 g of propylene glycol monomethyl ether acetate (PGMEA) was added to the residue, and the solvent was removed under reduced pressure to perform PGMEA replacement. Thereby, a PGMEA solution of the resist underlayer film-forming compound (A-15) which is a polyether compound was obtained.

[0445] (A-15): Mw = 3230

[0446] [Chemistry 49]

[0447]

[0448] [Synthesis Example 16] Synthesis of Compound (A-16) for Forming Resist Underlayer Film

[0449] A PGMEA solution of a polyether compound (A-16) for forming a resist underlayer film was obtained in the same manner as in Synthesis Example 7, except that the amount of the polyetherizing agent (G1) used in Synthesis Example 7 was changed to 2.5 g and 3.5 g of the polyetherizing agent (G3) was further used.

[0450] (A-16): Mw = 4344

[0451] [Chemistry 50]

[0452]

[0453] [Synthesis Example 17] Synthesis of Compound (A-17) for Forming Resist Underlayer Film

[0454] A PGMEA solution of a resist underlayer film-forming compound (A-17) which is a polyether compound was obtained in the same manner as in Synthesis Example 11 except that the amount of the polyetherifying agent (G3) used was changed to 10.6 g.

[0455] (A-17): Mw = 13500

[0456] [Chemistry 51]

[0457]

[0458] [Comparative Synthesis Example 1] Synthesis of Resist Underlayer Film-Forming Compound (R-1)

[0459] 10.0 g of 1,7-dihydroxynaphthalene, 4.8 g of a 37% aqueous solution of formaldehyde, 0.3 g of p-toluenesulfonic acid monohydrate, and 30 g of PGME were mixed, and the mixture was stirred at 120°C for 20 hours. The obtained mixture was washed twice with 200 ml of MIBK and 150 ml of water. The solvent was removed from the mixture under reduced pressure, and then 200 g of dimethylformamide was added to the residue, and the solvent was removed again under reduced pressure. Thereafter, 19.0 g of potassium carbonate and 80 g of additional DMF were added to the residue, and the mixture was stirred at 55°C, and 20.4 g of an etherifying agent (R1-2) was added dropwise thereto, and the mixture was reacted for 20 hours. The reaction product was returned to room temperature, washed with 300 ml of MIBK and 200 ml of water, and washed with 150 ml of a 3% aqueous solution of nitric acid. Then, the reaction product was washed four times with 200 ml of water, the solvent was removed under reduced pressure, 300 g of PGMEA was added to the residue, and the solvent was removed under reduced pressure to perform PGMEA substitution. Thus, a PGMEA solution of the resist underlayer film-forming compound (R-1) was obtained.

[0460] (R-1): Mw = 5324

[0461] [Chemistry 52]

[0462]

[0463] [Comparative Synthesis Example 2] Synthesis of Resist Underlayer Film-Forming Compound (R-2)

[0464] 10.0 g of 1,5-dihydroxynaphthalene, 10.13 g of 4-tert-butylbenzaldehyde, 50 g of PGMEA, and 1.2 g of methanesulfonic acid were mixed and reacted at 150°C for 2 hours. After the reaction was terminated, the reaction solution was added dropwise to a mixed solution of methanol / water, reprecipitated, and the supernatant was decanted. 100 g of PGMEA was added to the residue, and the solvent was replaced by drying under reduced pressure. In this way, a PGMEA solution of a compound (R-2) for forming a resist lower film was obtained.

[0465] (R-2): Mw = 4110

[0466] [Chemistry 53]

[0467]

[0468] [Comparative Synthesis Example 3] Synthesis of Resist Underlayer Film-Forming Compound (R-3)

[0469] 10.0 g of phenylnaphthylamine, 8.2 g of 9-fluorenone, 1.3 g of methanesulfonic acid, and 20 g of propylene glycol monomethyl ether acetate were mixed. Then, the mixture was heated under a nitrogen atmosphere until reflux and reacted for 14 hours. After the reaction stopped, the reaction product was reprecipitated with methanol, the upper layer was decanted, 100 g of PGMEA was added to the residue and dried under reduced pressure. In this way, a PGMEA solution of a compound (resin) (R-3) for forming a resist lower film was obtained.

[0470] (R-3): Mw = 1900

[0471] [Chemistry 54]

[0472]

[0473] [Preparation of Resist Underlayer Film Forming Composition UDL-1]

[0474] The resin (A-1) was dissolved in propylene glycol monomethyl ether acetate (PGMEA) containing 0.5 mass % of surfactant FC-4430 (manufactured by Sumitomo 3M Co., Ltd.) in the proportions shown in Table 1, and the obtained mixture was filtered with a 0.02 μm membrane filter to prepare a resist underlayer film forming composition (UDL-1).

[0475] [Preparation of Resist Underlayer Film-forming Compositions (UDL-2 to 24) and Resist Underlayer Film-forming Compositions for Comparative Examples (Comparative Examples UDL-1 to 3)]

[0476] The types and contents of each component were set as shown in Table 1. Other than that, each solution was adjusted in the same manner as UDL-1. In Table 1, "-" indicates that the corresponding component was not used. For the comparative compound (R-4), polyethylene glycol monomethyl ether acrylate (n = about 13) produced by Tokyo Chemical Industry Co., Ltd. was used. For the cross-linking agent, the following formula (D-1) was used, for the thermally decomposable resin, the following formula (E-1) was used, for the high boiling point solvent, 1,6-diacetoxyhexane (B2-1): boiling point 260°C was used, and for the thermal acid generator, the following formula (TAG-1) was used.

[0477] [Comparative Example Compound]

[0478] The comparative compound (R-4) is shown below.

[0479] [Chemistry 55]

[0480]

[0481] [Crosslinking agent]

[0482] The cross-linking agent (D-1) used in the resist underlayer film forming composition is shown below.

[0483] [Chemistry 56]

[0484]

[0485] [Synthesis Example of Pyrolyzable Resin] Synthesis of Pyrolyzable Resin (E-1)

[0486] 100 g of diethylene glycol monovinyl ether was added to a mixture of 3.8 g of cation exchange resin (Amberlyst (registered trademark) 15) and 100 g of ethyl acetate at room temperature, and the mixture was stirred for another 3 hours. 0.8 g of triethylamine was added to the obtained mixture, and after the reaction was stopped, the cation exchange resin was removed by filtration. The filtrate was concentrated under reduced pressure to obtain 100 g of a thermally decomposable resin (E-1) in the form of a highly viscous liquid.

[0487] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC, and the results were as follows: Mw = 5,200, Mw / Mn = 2.64.

[0488] [Chemistry 57]

[0489]

[0490] [Thermal acid generator]

[0491] The thermal acid generator (TAG-1) used in the resist underlayer film forming composition is shown below.

[0492] [Chemistry 58]

[0493]

[0494] [Table 1]

[0495]

[0496]

[0497] [Solvent resistance test]

[0498] The resist underlayer film-forming compositions (UDL-1 to 26, comparative examples UDL-1 to 4) prepared above were applied to silicon substrates to obtain coating films. The obtained coating films were fired at 180° C. for 60 seconds and then fired at 350° C. for 60 seconds. Thus, each resist underlayer film having a film thickness of about 200 nm was formed.

[0499] The film thickness (FT-1 [nm]) of the formed resist underlayer film was measured. Then, OK73 diluent (propylene glycol monomethyl ether / propylene glycol monomethyl ether acetate = 7 / 3) was placed on the resist underlayer film, and then allowed to stand for 30 seconds. The resist underlayer film was then spin-dried, and then the resist underlayer film was baked at 100°C for 60 seconds to evaporate the OK73 diluent (rework). The film thickness (FT-2 [nm]) of the resist underlayer film after rework was measured in this manner.

[0500] The difference in film thickness before and after the treatment was determined (residual film ratio: (FT-2 / FT-1)×100). The results are shown in Table 2 below.

[0501] [Contact angle measurement / hardness measurement]

[0502] The resist underlayer film-forming compositions (UDL-1 to 26, comparative examples UDL-1 to 4) prepared above were applied to a silicon substrate to obtain coating films. The coating films were then fired at 180° C. for 60 seconds and then fired at 350° C. for 60 seconds. Thus, each resist underlayer film having a film thickness of about 200 nm was formed.

[0503] The contact angle of the resist underlayer films with pure water was measured. The hardness of the resist underlayer films was measured by nanoindentation test using a nanoindenter SA2 manufactured by TOYO Corporation. The results are shown in Table 2.

[0504] [Table 2]

[0505]

[0506]

[0507] As shown in Table 2, the residual film rates ((FT-2 / FT-1)×100) before and after reworking of the resist underlayer film forming compositions (Examples 1-1 to 1-26) of the present invention all exceeded 101%, indicating that the films after firing have become porous films having a large number of pores into which a diluent such as OK73 can penetrate. In addition, the residual film rates ((FT-2 / FT-1)×100) of Examples 1-9 to 1-17 using a polyether compound having a spirocyclic structure in the parent core exceeded 102%, indicating that the porosity is further improved by the effects of the cyclic alkyl structure and cyclic alkyl ether of the parent core. In addition, Examples 1-18 to 1-20 to which a crosslinking agent is added have a slightly suppressed residual film rate ((FT-2 / FT-1)×100) before and after reworking compared to corresponding examples such as Examples 1-6, 1-9, and 1-11 to which no crosslinking agent is added. In Examples 1-21 to 1-23, in which a pyrolyzable resin was added, the residual film ratio ((FT-2 / FT-1)×100) before and after reworking increased compared to the corresponding examples 1-6, 1-9, and 1-11, in which no pyrolyzable resin was added. This shows that the porosity can be adjusted by adding a crosslinking agent and a pyrolyzable resin.

[0508] In Comparative Example 1-1 of the novolac resin in which an ether substituent was introduced using the same mother core and Comparative Example 1-2 of the novolac resin in which the hydroxyl group remained as it was, no improvement in the residual film ratio was observed. These results indicate that the polyether structure is important for making the material porous.

[0509] The residual film ratio of Comparative Example 1-3 was 99.9%, which was significantly low.

[0510] In Comparative Example 1-4 using a polyether compound not containing an aromatic ring, sublimation was so intense that various measurements could not be performed. This confirmed that the introduction of an aromatic ring is effective for purposes such as suppression of sublimates in addition to processing resistance.

[0511] In addition, the contact angles of Example 1-1 in which fluorine was introduced and Example 1-2 in which fluorine was not introduced differed by about 10 degrees, and it was confirmed that the gas used can be used flexibly according to its hydrophilicity and hydrophobicity.

[0512] In Examples 1-1 to 1-26, the hardness measured as an index of processing resistance exceeded 0.55 GPa, and some exceeded 0.7 GPa, confirming that they also had sufficient processing resistance.

[0513] [Landfill characteristics evaluation]

[0514] The resist underlayer film-forming compositions prepared above (UDL-1 to 26, comparative examples UDL-2 to 3) were coated on SiO2 wafer substrates having a dense hole pattern (hole diameter 0.16 μm, hole depth 0.50 μm, and distance between the centers of two adjacent holes 0.32 μm), and the coated films were fired at 180° C. for 60 seconds and then fired at 350° C. for 60 seconds. Thus, each resist underlayer film with a film thickness of 200 nm was formed on the substrate having a dense hole pattern.

[0515] The cross-sectional shape of each wafer substrate obtained was observed using an electron microscope (S-4700) manufactured by Hitachi, Ltd. to confirm whether there are no pores (voids) inside the holes and whether they are filled with organic films. The results are shown in Table 3 below. When a composition for forming a resist underlayer film with poor filling characteristics is used, pores will be generated inside the holes. When a composition for forming a resist underlayer film with good filling characteristics is used, in this evaluation, the organic film is filled inside the holes without pores. The evaluation is as follows. A: No pores and can be filled, B: There are tiny pores, C: There are pores or it cannot be filled.

[0516] [Table 3]

[0517]

[0518]

[0519] As shown in Table 3, in Examples 2-1 to 2-26 using the resist underlayer film forming composition (UDL-1 to 26) of the present invention, no voids were generated except for Example 2-17, and a dense hole pattern was filled, confirming that good filling characteristics could be achieved. Example 2-17, in which voids were confirmed, used a polymer with a molecular weight of 13,500, and it was believed that the molecular weight was too large to fill well to the bottom, so voids were observed. In addition, even in the composition to which a crosslinking agent or a thermally decomposable resin was added, voids were not observed.

[0520] Comparative Example 2-1 using Comparative Example UDL-2 failed to fill the micropattern. This is believed to be because the compound R-2 in Comparative Example UDL-2 has no ether substituent and maintains a rigid resin structure, so the resin has low fluidity and cannot fill the micropattern.

[0521] In Comparative Example 2-2 using Comparative Example UDL-3, larger pores were observed at the bottom than in Example 2-17. This is believed to be because the resin of Comparative Example UDL-3 does not have crosslinking properties in itself, but a large amount of crosslinking agent, thermal acid generator, etc. are added, resulting in a large amount of decomposition of the resin and additives and sublimation products.

[0522] [Planarization characteristics evaluation]

[0523] The resist lower film forming composition prepared above is coated on a SiO2 wafer substrate having a huge isolated trench pattern (trench width 10μm, trench depth 0.1μm), and the obtained coating film is fired at 180°C for 60 seconds, and then fired at 350°C for 60 seconds. In this way, each resist lower film is formed on a substrate having a huge isolated trench pattern. The height difference of the resist lower film between the trench part and the non-trench part is observed using the NX10 atomic force microscope (AFM) manufactured by Park Systems. The results are shown in Table 4. In this evaluation, it can be said that the smaller the height difference, the better the flattening characteristics. In addition, in this evaluation, the trench pattern with a depth of 0.10μm is flattened using an organic film forming composition with a usual film thickness of about 0.2μm. In order to evaluate the pros and cons of the flattening characteristics, strict evaluation conditions are set.

[0524] [Table 4]

[0525]

[0526] As shown in Table 4, Examples 3-1 to 3-5, which respectively used resist underlayer film forming compositions (UDL-6, 9, 11, 15 and 16) which are examples of the present invention, were confirmed to have very excellent flatness compared to Comparative Example 3-3, which had a very different resin structure. It was also confirmed that the height difference between the pattern portion and the non-pattern portion of the film was small and the flattening characteristics were excellent compared to Comparative Examples 3-1 and 3-2, which used the same mother core to make the novolac resin. Examples 3-4 to 3-5, which used poly-Ar1 structure and R1 structure (UDL-15 and 16), were the result of improved flatness. It is believed that this is the result of promoting fluidity by combining the two. When comparing Examples 3-6 to 11 and Example 3-14, which added a crosslinking agent (D-1) and a pyrolyzable resin (E-1), with Examples 3-1 to 3-3, which did not add such a crosslinking agent, there was no significant change in flatness, and it is believed that the addition of a crosslinking agent and a pyrolyzable resin that can adjust the porosity of the film has no effect on flatness. In Examples 3-12 and 3-13, in which a high boiling point solvent (B2-1) was added, the flatness was improved compared to Examples 3-2 and 3-3 in which no high boiling point solvent was added. This is considered to be because the high boiling point solvent improves the thermal fluidity.

[0527] As described above, the resist underlayer film forming composition of the present invention can form a film that can be used as an underlayer film, exhibits high degree of embedding and planarization characteristics, has high hardness and excellent processing resistance, and is porous and low-density, so that a resist underlayer film with excellent air permeability can be provided. Such a resist underlayer film is particularly useful in nanoimprinting method and is also suitable for use in multilayer resist process.

[0528] This manual contains the following aspects.

[0529] [1] A composition for forming a resist underlayer film, comprising:

[0530] (A) a polyether compound containing a repeating unit represented by the following general formula (I), and

[0531] (B) an organic solvent;

[0532] [Chemistry 59]

[0533]

[0534] In the general formula (I), Ar1 is a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, a substituted or unsubstituted heteroaryl group having 6 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 30 carbon atoms formed by condensation or bonding with an aliphatic ring or heterocyclic ring, or a substituted or unsubstituted aryl group having 6 to 30 carbon atoms bonded to each other via a linear, branched or cyclic hydrocarbon group, an ether group or a carbonyl group. Ar1 may be one or a combination of multiple groups in the same resin. R1 is a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, or a substituted or unsubstituted linear hydrocarbon group having 1 to 20 carbon atoms. R2 is any one of a substituted or unsubstituted straight-chain, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom; R3 in the same resin may be one or a combination of multiple groups, and is a hydrogen atom, a substituted or unsubstituted straight-chain, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted straight-chain, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted straight-chain, branched or cyclic alkynyl group having 2 to 20 carbon atoms; and n and m are integers greater than 0.

[0535] [2] The resist underlayer film forming composition according to [1], wherein in the general formula (I), at least one of the R3 is a structure R selected from the group consisting of the groups shown in the following formula (II-1): II-1 , and in the structure R II-1 When the ratio is set to a, 1≤a≤100;

[0536] [Chemistry 60]

[0537]

[0538] In the formula (II-1), * represents a bonding site with an oxygen atom.

[0539] [3] The resist underlayer film forming composition according to [1], wherein in the general formula (I), R3 is a structure R selected from the group consisting of the groups shown in the following formula (II-1): II-1 and a structure R selected from the group consisting of groups represented by the following formula (II-2): II-2 combination, and in the structure R II-1 The ratio is set to a, and the structure R II-2 When the ratio is set to b, the relationship of 1≤a≤99, 1≤b≤99, and a+b=100 is satisfied;

[0540] [Chemistry 61]

[0541]

[0542] In formula (II-1) and formula (II-2), * represents a bonding site with an oxygen atom.

[0543] [4] The resist underlayer film forming composition according to any one of [1] to [3], wherein in the general formula (I), R1 is selected from the group consisting of groups represented by the following general formulae (III-1) to (III-3);

[0544] [Chemistry 62]

[0545]

[0546] In formulae (III-1) to (III-3), * represents a bonding site to an oxygen atom.

[0547] [5] The resist underlayer film forming composition according to any one of [1] to [4], wherein in the general formula (I), Ar1 is selected from the group consisting of the structures represented by the following formula (Ar-1);

[0548] [Chemistry 63]

[0549]

[0550] In the formula (Ar-1), * represents a bonding site to the oxygen atom of -O-R1- or OR3.

[0551] [6] The resist underlayer film-forming composition according to any one of [1] to [5], wherein the polyether compound has a polystyrene-equivalent weight average molecular weight Mw of 2,000 to 12,000 as determined by gel permeation chromatography.

[0552] [7] The resist underlayer film forming composition as described in any one of [1] to [6], wherein the thickness of a coating film obtained by applying the resist underlayer film forming composition to a substrate, firing the coating film at 180°C for 60 seconds, and then additionally firing the coating film at 350°C for 60 seconds is defined as FT-1, and after the additional firing, an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is placed on the coating film, followed by allowing the mixture to stand for 30 seconds, and then the coating film is spin-dried and then baked at 100°C for 60 seconds to evaporate the OK73 diluent is defined as FT-2,

[0553] It becomes 101<{(FT-2) / (FT-1)}×100.

[0554] [8] The resist underlayer film forming composition according to any one of [1] to [7], further comprising (C) a surfactant.

[0555] [9] The resist underlayer film forming composition of any one of [1] to [6] further comprises (D) a cross-linking agent, wherein the resist underlayer film forming composition is applied to a substrate to obtain a coating film, the coating film is subjected to firing at 180°C for 60 seconds, and then subjected to additional firing at 350°C for 60 seconds, and the film thickness of the coating film is defined as FT-1, and after the additional firing, an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is placed on the coating film, the mixture is allowed to stand for 30 seconds, the coating film is spin-dried, and then the coating film is subjected to baking at 100°C for 60 seconds to evaporate the OK73 diluent, and the film thickness of the coating film is defined as FT-2,

[0556] It becomes 100<{(FT-2) / (FT-1)}×100<103.

[0557]

[10] The resist underlayer film forming composition according to any one of [1] to [6] further comprises (E) a thermally decomposable resin, wherein the resist underlayer film forming composition is applied to a substrate to obtain a coating film, the coating film is subjected to firing at 180°C for 60 seconds, and then subjected to additional firing at 350°C for 60 seconds, and the film thickness of the coating film is defined as FT-1, and after the additional firing, an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is placed on the coating film, the mixture is allowed to stand for 30 seconds, the coating film is spin-dried, and the coating film is then subjected to baking at 100°C for 60 seconds to evaporate the OK73 diluent, and the film thickness of the coating film is defined as FT-2,

[0558] It becomes 101.5<{(FT-2) / (FT-1)}×100.

[0559]

[11] The resist underlayer film forming composition of any one of [1] to [6] further comprises both (D) a crosslinking agent and (E) a thermally decomposable resin, wherein the resist underlayer film forming composition is applied to a substrate to obtain a coating film, the coating film is subjected to firing at 180°C for 60 seconds, and then subjected to additional firing at 350°C for 60 seconds, and the film thickness of the coating film is defined as FT-1, and after the additional firing, an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3 is placed on the coating film, the mixture is allowed to stand for 30 seconds, the coating film is spin-dried, and then the coating film is subjected to baking at 100°C for 60 seconds to evaporate the OK73 diluent, and the film thickness of the coating film is defined as FT-2,

[0560] It becomes 100<{(FT-2) / (FT-1)}×100.

[0561]

[12] The resist underlayer film forming composition according to any one of [1] to

[11] , further comprising (F) an acid generator.

[0562]

[13] The resist underlayer film forming composition according to any one of [1] to

[12] , wherein the resist underlayer film forming composition is for nanoimprinting.

[0563]

[14] A resist underlayer film characterized by being a cured product of a coating film composed of the resist underlayer film forming composition as described in any one of [1] to

[12] .

[0564]

[15] A method for manufacturing a resist underlayer film, characterized in that it includes the following steps: applying a resist underlayer film-forming composition as described in any one of [1] to

[12] on a semiconductor substrate to obtain a coating film, and firing the coating film to obtain a resist underlayer film.

[0565]

[16] A pattern forming method, characterized in that it includes the following steps: forming a resist underlayer film on a semiconductor substrate from a resist underlayer film forming composition as described in any one of [1] to

[12] , forming a curable composition film on the resist underlayer film, bringing the curable composition film into contact with a mold, irradiating the curable composition film with light or an electron beam to form a hardened film, and separating the hardened film from the mold.

[0566]

[17] A pattern forming method as described in

[16] , wherein the step of forming a curable composition film on the resist underlayer film comprises: forming a bonding layer and / or a polysilicon oxide layer containing less than 99 mass % of Si on the resist underlayer film by coating or evaporation, and forming a curable composition film thereon.

[0567]

[18] A method for manufacturing a semiconductor device, characterized in that it includes the following steps: forming a resist underlayer film on a semiconductor substrate from a resist underlayer film forming composition such as any one of [1] to

[12] , forming a resist film on the resist underlayer film, irradiating the resist film with light or an electron beam, and then developing it to form a resist pattern, using the formed resist pattern as a mask to etch the resist underlayer film to obtain a patterned underlayer film, and processing the semiconductor substrate using the patterned underlayer film as a mask.

[0568]

[19] A method for manufacturing a semiconductor device, characterized in that it includes the following steps: forming a resist underlayer film on a semiconductor substrate from a resist underlayer film forming composition such as any one of [1] to

[12] , forming a hard mask on the resist underlayer film, and then forming a resist film on the hard mask, irradiating the resist film with light or an electron beam, and then developing it to form a resist pattern, using the formed resist pattern as a mask to etch the hard mask to obtain a patterned hard mask, using the patterned hard mask as a mask to etch the underlayer film to obtain a patterned resist underlayer film, and using the patterned resist underlayer film as a mask to process the semiconductor substrate.

[0569] The present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and those having the technical ideas and substantially the same configurations described in the claims of the present invention and having the same functions and effects are all included in the technical scope of the present invention.

Claims

1. A composition for forming a resist underlayer film, characterized in that: Include: (A) a polyether compound containing a repeating unit represented by the following general formula (I), and (B) an organic solvent; In the general formula (I), Ar1 is a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, a substituted or unsubstituted heteroaryl group having 6 to 30 carbon atoms, a substituted or unsubstituted aryl group having 6 to 30 carbon atoms formed by condensation or bonding with an aliphatic ring or heterocyclic ring, or a substituted or unsubstituted aryl group having 6 to 30 carbon atoms bonded to each other via a linear, branched or cyclic hydrocarbon group, an ether group or a carbonyl group. Ar1 may be one or a combination of multiple groups in the same resin. R1 is a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms, or a substituted or unsubstituted linear, branched or cyclic saturated or unsaturated divalent hydrocarbon group having 1 to 20 carbon atoms. R2 is any one of a substituted or unsubstituted straight-chain, branched or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, a substituted or unsubstituted heteroalkyl group having 1 to 20 carbon atoms, an amino group, a thiol group, or a halogen atom; R3 in the same resin may be one or a combination of multiple groups, and is a hydrogen atom, a substituted or unsubstituted straight-chain, branched or cyclic alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted straight-chain, branched or cyclic alkenyl group having 2 to 20 carbon atoms, or a substituted or unsubstituted straight-chain, branched or cyclic alkynyl group having 2 to 20 carbon atoms; and n and m are integers greater than 0.

2. The resist underlayer film forming composition according to claim 1, wherein In the general formula (I), at least one of the R3 is a structure R selected from the group consisting of the groups shown in the following formula (II-1): II-1 , and in the structure R II-1 When the ratio is set to a, 1≤a≤100; In the formula (II-1), * represents a bonding site with an oxygen atom.

3. The resist underlayer film forming composition according to claim 1, wherein In the general formula (I), R3 is a structure R selected from the group consisting of the groups shown in the following formula (II-1): II-1 and a structure R selected from the group consisting of groups represented by the following formula (II-2): II-2 combination, and in the structure R II-1 The ratio is set to a, and the structure R II-2 When the ratio is set to b, the relationship of 1≤a≤99, 1≤b≤99, and a+b=100 is satisfied; In formula (II-1) and formula (II-2), * represents a bonding site with an oxygen atom.

4. The resist underlayer film forming composition according to claim 1, wherein In the general formula (I), R1 is selected from the group consisting of the groups shown in the following general formulas (III-1) to (III-3); In formulae (III-1) to (III-3), * represents a bonding site to an oxygen atom.

5. The resist underlayer film forming composition according to claim 1, wherein In the general formula (I), Ar1 is selected from the group consisting of the structures shown in the following formula (Ar-1); In the formula (Ar-1), * represents a bonding site to the oxygen atom of -O-R1- or OR3.

6. The resist underlayer film forming composition according to claim 1, wherein The polyether compound has a polystyrene-equivalent weight average molecular weight Mw of 2,000 to 12,000 as determined by gel permeation chromatography.

7. The resist underlayer film forming composition according to claim 1, wherein The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to firing at 180° C. for 60 seconds, and then subjected to additional firing at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and After the additional firing, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2. It becomes 101<{(FT-2) / (FT-1)}×100. 8 . The resist underlayer film forming composition according to claim 1 , further comprising (C) a surfactant.

9. The resist underlayer film forming composition according to claim 1, further comprising (D) a crosslinking agent, The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to firing at 180° C. for 60 seconds, and then subjected to additional firing at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and After the additional firing, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2. It becomes 100<{(FT-2) / (FT-1)}×100<103.

10. The resist underlayer film forming composition according to claim 1, further comprising (E) a thermally decomposable resin, The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to firing at 180° C. for 60 seconds, and then subjected to additional firing at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and After the additional firing, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2. It becomes 101.5<{(FT-2) / (FT-1)}×100.

11. The resist underlayer film forming composition according to claim 1, further comprising both (D) a crosslinking agent and (E) a thermally decomposable resin. The resist underlayer film-forming composition is applied to a substrate to obtain a coating film, and the coating film is subjected to firing at 180° C. for 60 seconds, and then subjected to additional firing at 350° C. for 60 seconds. The film thickness of the coating film is defined as FT-1, and After the additional firing, the coating film is provided with an OK73 diluent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a ratio of 7:3, and then left to stand for 30 seconds. The coating film is then spin-dried, and then the coating film is baked at 100° C. for 60 seconds to evaporate the OK73 diluent. The film thickness of the coating film is defined as FT-2. It becomes 100<{(FT-2) / (FT-1)}×100. 12 . The resist underlayer film forming composition according to claim 1 , further comprising (F) an acid generator.

13. The resist underlayer film forming composition according to any one of claims 1 to 12, wherein The resist underlayer film forming composition is used for nanoimprinting.

14. A resist underlayer film, characterized in that: A cured product of a coating film composed of the resist underlayer film forming composition according to any one of claims 1 to 12.

15. A method for manufacturing a resist underlayer film, characterized in that: The following steps are involved: The resist underlayer film forming composition according to any one of claims 1 to 12 is applied onto a semiconductor substrate to obtain a coating film, The coated film is fired to obtain a resist underlayer film.

16. A method for forming a pattern, characterized in that: The following steps are involved: forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition according to any one of claims 1 to 12, forming a hardening composition film on the resist underlayer film, The curable composition film is brought into contact with a mold, The curable composition film is irradiated with light or electron beam to form a cured film. The cured film is separated from the mold.

17. The pattern forming method according to claim 16, wherein: The step of forming a hardening composition film on the resist underlayer film comprises: An adhesion layer and / or a polysilicon oxide layer containing 99 mass % or less of Si is formed on the resist underlayer film by coating or vapor deposition, and a curable composition film is formed thereon.

18. A method for manufacturing a semiconductor device, characterized in that: The following steps are involved: forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition according to any one of claims 1 to 12, forming a resist film on the resist underlayer film, The resist film is irradiated with light or electron beams and then developed to form a resist pattern. Using the formed resist pattern as a mask, the resist underlayer film is etched to obtain a patterned underlayer film, The semiconductor substrate is processed using the patterned underlying film as a mask.

19. A method for manufacturing a semiconductor device, characterized in that: The following steps are involved: forming a resist underlayer film on a semiconductor substrate using the resist underlayer film-forming composition according to any one of claims 1 to 12, forming a hard mask on the resist underlayer film, Then, a resist film is formed on the hard mask film. The resist film is irradiated with light or electron beams and then developed to form a resist pattern. The hard mask is etched using the formed resist pattern as a mask to obtain a patterned hard mask, Using the patterned hard mask film as a mask, the lower layer film is etched to obtain a patterned resist lower layer film, The semiconductor substrate is processed using the patterned resist underlayer film as a mask.

Citation Information

Patent Citations

  • Virtual-addressing device for a computer

    EP0010185A1

  • Copying machine (metal cutting)

    IE10958L

  • Image transferring drum

    JP1983027180A

  • Method for forming graded structures using imprint lithography

    JP2006524919A

  • Photoresist underlayer film forming material and pattern forming method

    JP2007199653A